3D Traction Forces in Cancer Cell Invasion - Koch, Thorsten; Münster, Stefan; Bonakdar, Navid; Butler, James P.; Fabry, Ben (PLoS ONE, 2012)

A Blind Spot in Confocal Reflection Microscopy: The Dependence of Fiber Brightness on Fiber Orientation in Imaging Biopolymer Networks - Jawerth, Louise M.; Münster, Stefan; Vader, David A.; Fabry, Ben; Weitz, David A. (Journal of Biophysics, 2009)

Acquisition of paclitaxel resistance is associated with a more aggressive and invasive phenotype in prostate cancer - Kim, John J.; Yin, Bo; Christudass, Christhunesa S.; Terada, Naoki; Rajagopalan, Krithika; Fabry, Ben; Lee, Danielle Y.; Shiraishi, Takumi; Getzenberger, Robert H.; Veltri, Robert W.; An, Steven S.; Mooney, Steven M. (Journal of Cellular Biochemistry, 2013)

Activation and regulation of endogenous retroviral genes in the human pituitary gland and related endocrine tumours - Buslei, R.; Strissel, Pamela; Henke, Christine; Schey, Regina; Lang, Nadine; Ruebner, M.; Stolt, Claus; Fabry, Ben; Buchfelder, Michael; Strick, Reiner (Neuropathology and Applied Neurobiology, 2015)
Adenohypophysis (AH) hormone-producing cells represent the origin of diverse groups of pituitary adenomas (PA). Deregulation of hypothalamic hormone receptors, growth factors and cAMP signalling have been implicated in the aetiology of PA. Endogenous retroviruses (ERVs) are derived from past exogenous retroviral infections and represent more than 8% of the human genome. Some ERV genes encode open reading frames and produce functional proteins, for example, the ERVW-1 envelope gene Syncytin-1, essential for placentogenesis, but also deregulated in human tumours. Data concerning ERV expression in the AH and related endocrine tumours are missing.Syncytin-1 protein was analysed in normal AH (n = 15) and compared with five PA subtypes (n = 117) by immunohistochemistry. Absolute gene expression of 20 ERV functional envelope genes and ERVW-5 gag was measured. PA tissues were examined for Syncytin-1 and the cAMP signalling marker phospho-CREB-Ser133 using immunohistochemistry. Isolated primary human PA cells were treated with different hormones. Murine embryonic and adult pituitary gland ERV expressions were compared with human AH.Syncytin-1 protein colocalized with corticotropic cells of AH. In contrast, all PA demonstrated significant Syncytin-1 protein overexpression, supporting deregulation. All other ERV genes showed significant up-regulations in different PA subtypes. Phospho-CREB-Ser133 and Syncytin-1 colocalized in PA cells. Cultivated primary PA cells with ACTH or CRH induced their respective receptors and ERV genes. Syncytin-A/-B, murine orthologues to human Syncytin-1/-2, localized to embryonic and adult pituitary glands demonstrating functional mammalian conservation.Deregulated ERV genes may contribute to PA development via cAMP signalling.
EVALuna2:4955

Active soft glassy rheology of adherent cells - Kollmannsberger, Philip; Fabry, Ben (Soft Matter, 2009)

Adaptive stochastic resonance for unknown and variable input signals - Krauß, Patrick; Metzner, Claus; Schilling, Achim; Schütz, Christian; Tziridis, Konstantin; Fabry, Ben; Schulze, Holger (Scientific Reports, 2017)

[Added work of breathing, respiratory pattern and determination of ventilator weaning readiness in inspiratory pressure support and and automatic tube compensation] - Stocker, R.; Fabry, Ben; et al. (Unfallchirurg, 1996)

Additional inspiratory work of breathing imposed by tracheostomy tubes and non-ideal ventilator properties in critically ill patients - Haberthür, Christoph; Fabry, Ben; Stocker, R.; Ritz, Beate; Guttmann, Josef (Intensive Care Medicine, 1999)

A finite element model of cell deformation during magnetic bead twisting - Mijailovich, Srboljub M; Kojic, Milos; Zivkovic, Miroslav; Fabry, Ben; Fredberg, Jeffrey (JPN J PHYSIOL, 2002)

Airway Hyperresponsiveness, Remodeling, and Smooth Muscle Mass: Right Answer, Wrong Reason? - Oliver, Madavi; Fabry, Ben; Marinkovic, Aleksandar; Mijailovich, Srboljub M; Butler, James P.; Fredberg, Jeffrey (American Journal of Respiratory Cell and Molecular Biology, 2007)

Airway smooth muscle dynamics: a common pathway of airway obstruction in asthma - Seow, Chun Y.; An, Steven S.; Bai, T. R.; Bates, JHT; Black, J. L.; Brown, R.H.; Brusasco, Vito; Chitano, Pasquale; Deng, L.; Dowell, M.; Eidelman, D.H.; Fabry, Ben; et al. (European Respiratory Journal, 2007)

Akt and p53 are potential mediators of reduced mammary tumor growth by Chloroquine and the mTOR inhibitor RAD001 - Löhberg, Christian; Strissel, Pamela; Dittrich, Ralf; Strick, Reiner; Dittmer, Jürgen; Dittmer, Angela; Fabry, Ben; Kalender, Willi Alfred; Koch, Thorsten; Wachter, David; Groh, Nicole; Polier, Astrid; et al. (Biochemical Pharmacology, 2012)

Akt and p53 are potential mediators of reduced mammary tumor growth by Chloroquine and the mTOR inhibitor RAD001 - Löhberg, Christian; Strissel, Pamela; Dittrich, Ralf; Strick, Reiner; Dittmer, Jürgen; Dittmer, Angela; Fabry, Ben; Kalender, Willi Alfred; Koch, Thorsten; Wachter, David; Groh, Nicole; Polier, Astrid; et al. (Biochemical Pharmacology, 2012)

Alginate-based hydrogels with improved adhesive properties for cell encapsulation - Sarker, Bapi; Rompf, Julia; Silva, Raquel; Lang, Nadine; Detsch, Rainer; Kaschta, Joachim; Fabry, Ben; Boccaccini, Aldo R. (International Journal of Biological Macromolecules, 2015)
Hydrogel-based biomaterials are ideal scaffolding matrices for microencapsulation, but they need to be modified to resemble the mechanical, structural and chemical properties of the native extracellular matrix. Here, we compare the mechanical properties and the degradation behavior of unmodified and modified alginate hydrogels in which cell adhesive functionality is conferred either by blending or covalently cross-linking with gelatin. Furthermore, we measure the spreading and proliferation of encapsulated osteoblast-like MG-63 cells. Alginate hydrogels covalently crosslinked with gelatin show the highest degree of cell adhesion, spreading, migration, and proliferation, as well as a faster degradation rate, and are therefore a particularly suitable material for microencapsulation.
Keywords: Alginate; Cell encapsulation; Hydrogel

A low-cost uniaxial cell stretcher for six parallel wells - Kah, Delf-Thorge Eric; Winterl, Alexander; Přechová, Magdalena; Schöler, Ulrike; Schneider, Werner; Friedrich, Oliver; Gregor, Martin; Fabry, Ben (HardwareX, 2021)
Cells in the lungs, the heart, and numerous other organs, are constantly exposed to dynamic forces and deformations. To mimic these dynamic mechanical loading conditions and to study the resulting cellular responses such as morphological changes or the activation of biochemical signaling pathways, cells are typically seeded on flexible 2D substrates that are uniaxially or biaxially stretched. Here, we present an open-source cell stretcher built from parts of an Anet A8 3D printer. The cell stretcher is controlled by a fully programmable open-source software using GCode and Python. Up to six flexible optically clear substrates can be stretched simultaneously, allowing for comparative multi-batch biological studies including microscopic image analysis. The cell yield from the cell culture area of 4 cm2 per substrate is sufficient for Western-blot protein analysis. As a proof-of-concept, we study the activation of the Yes-associated protein (YAP) mechanotransduction pathway in response to increased cytoskeletal tension induced by uniaxial stretching of epithelial cells. Our data support the previously observed activation of the YAP transcription pathway by stretch-induced increase in cytoskeletal tension and demonstrate the suitability of the cell stretcher to study complex mechano-biological processes.
CRIS-Team Scopus Importer:2021-01-01
Keywords: 3D printer; Cell Mechanics; Cell stretcher; Mechanosensing; Uniaxial stretch; YAP

Analysis of cell mechanics in single vinculin-deficient cells using a magnetic tweezer - Alenghat, Francis J.; Fabry, Ben; Tsai, Kenneth; Goldmann, Wolfgang; Goldmann, Wolfgang; Ingber, Donald E. (Biochemical and Biophysical Research Communications, 2000)

An analysis of desynchronization between the spontaneously breathing patient and ventilator during inspiratory pressure support - Fabry, Ben; Guttmann, Josef; Eberhard, Luc; Bauer, Tilman; Haberthür, Christoph; Wolff, Gunther (Chest, 1995)

Anchorage of vinculin to lipid membranes influences cell mechanical properties - Diez, Gerold; Kollmannsberger, Philip; Mierke, Claudia; Koch, Thorsten; Vali, Hojatollah; Fabry, Ben; Goldmann, Wolfgang (Journal of Biophysics, 2009)

Anodic mesoporous TiO(2) layer on Ti for enhanced formation of biomimetic hydroxyapatite - Dey, Tuli; Roy, Poulumi; Fabry, Ben; Schmuki, Patrik (Acta Biomaterialia, 2010)
Ti surfaces can be very efficiently coated by a robust ( extgreekmm thick) mesoporous titania layer (MTL). These coatings are produced by anodization of Ti at elevated temperature in a glycerol/K2HPO4 electrolyte, followed by an appropriate etching process. In the present work we examine these layers with regard to their ability to form hydroxyapatite. Immersion tests in two types of simulated body fluids (Kokubo SBF and Bohner and Lemaitre SBF) combined with scanning electron microscopy, X-ray diffraction and X-ray photoelectron spectroscopy investigations show that these MTL layers lead to a significant enhancement of HAp formation and anchoring in the structure compared with non-coated or even nanotubular Ti surface coatings (these were recently reported to be the most efficient in terms of HAp formation).

Anodic Titanium Dioxide Nanotubes for Magnetically Guided Therapeutic Delivery - Hasanzadeh Kafshgari, Morteza; Kah, Delf-Thorge Eric; Mazare, Anca Valentina; Nguyen, Nhat Truong; Distaso, Monica; Peukert, Wolfgang; Goldmann, Wolfgang; Schmuki, Patrik; Fabry, Ben (Scientific Reports, 2019)
Hollow titanium dioxide (TiO2) nanotubes offer substantially higher drug loading capacity and slower drug release kinetics compared to solid drug nanocarriers of comparable size. In this report, we load TiO2 nanotubes with iron oxide nanoparticles to facilitate site-specific magnetic guidance and drug delivery. We generate magnetic TiO2 nanotubes (TiO2NTs) by incorporating a ferrofluid containing Ø ≈ 10 nm iron oxide nanoparticles in planar sheets of weakly connected TiO2 nanotubes. After thermal annealing, the magnetic tubular arrays are loaded with therapeutic drugs and then sonicated to separate the nanotubes. We demonstrate that magnetic TiO2NTs are non-toxic for HeLa cells at therapeutic concentrations (≤200 µg/mL). Adhesion and endocytosis of magnetic nanotubes to a layer of HeLa cells are increased in the presence of a magnetic gradient field. As a proof-of-concept, we load the nanotubes with the topoisomerase inhibitor camptothecin and achieve a 90% killing efficiency. We also load the nanotubes with oligonucleotides for cell transfection and achieve 100% cellular uptake efficiency. Our results demonstrate the potential of magnetic TiO2NTs for a wide range of biomedical applications, including site-specific delivery of therapeutic drugs.
CRIS-Team Scopus Importer:2019-09-27

Are environmental factors responsible for changed breeding behaviour in emperor penguins? - Paranhos Zitterbart, Daniel; Richter, Sebastian; Spiekermann, Georg; Behrens, Lisa K.; Regnery, Julia; Fontes, Renè P.; Hänssler, Thedda; König-Langlo, Gert; Weller, Rolf; Fabry, Ben (Antarctic Science, 2014)

A remote-controlled observatory for behavioural and ecological research: A case study on emperor penguins - Richter, Sebastian; Gerum, Richard; Schneider, Werner; Fabry, Ben; Le Bohec, Céline; Paranhos Zitterbart, Daniel (Methods in Ecology and Evolution, 2018)

A simplified implementation of the bubble analysis of biopolymer network pores - Münster, Stefan; Fabry, Ben (Biophysical Journal, 2013)

Bayesian inference of time varying parameters in autoregressive processes - Mark, Christoph; Metzner, Claus; Fabry, Ben (arXiv, 2014)

Bayesian model selection for complex dynamic systems - Mark, Christoph; Metzner, Claus; Lautscham, Lena; Strissel, Pamela; Strick, Reiner; Fabry, Ben (Nature Communications, 2018)
Time series generated by complex systems like financial markets and the earth's atmosphere often represent superstatistical random walks: on short time scales, the data follow a simple low-level model, but the model parameters are not constant and can fluctuate on longer time scales according to a high-level model. While the low-level model is often dictated by the type of the data, the high-level model, which describes how the parameters change, is unknown in most cases. Here we present a computationally efficient method to infer the time course of the parameter variations from time-series with short-range correlations. Importantly, this method evaluates the model evidence to objectively select between competing high-level models. We apply this method to detect anomalous price movements in financial markets, characterize cancer cell invasiveness, identify historical policies relevant for working safety in coal mines, and compare different climate change scenarios to forecast global warming.
EVALuna2:210064

Behavior of encapsulated MG-63 cells in RGD and gelatine-modified alginate hydrogels - Grigore, Alexandra; Sarker, Bapi; Fabry, Ben; Boccaccini, Aldo R.; Detsch, Rainer (Tissue Engineering - Part A, 2014)
Achieving cell spreading and proliferation inside hydrogels that are compatible with microencapsulation technology represents a major challenge for tissue engineering scaffolding and for the development of three-dimensional cell culture models. In this study, microcapsules of 650-900μm in diameter were fabricated from oxidized alginate covalently cross-linked with gelatine (AlGel). Schiff's base bond formed in AlGel, detected by Fourier transform infrared spectroscopy, which confirmed the cross-linking of oxidized alginate with gelatine. Biological properties of alginate based hydrogels were studied by comparing the viability and morphology of MG-63 osteosarcoma cells encapsulated in gelatine and RGD-modified alginate. We hypothesized that the presence of gelatine and RGD will support cell adhesion and spreading inside the microcapsules and finally, also vascular endothelial growth factor (VEGF) secretion. After 4 days of incubation, cells formed extensive cortical protrusions and after 2 weeks they proliferated, migrated, and formed cellular networks through the AlGel material. In contrast, cells encapsulated in pure alginate and in RGD-modified alginate formed spherical aggregates with limited cell mobility and VEGF secretion. Metabolic activity was doubled after 5 days of incubation, making AlGel a promising material for cell encapsulation. © Mary Ann Liebert, Inc.

Biologging of emperor penguins-Attachment techniques and associated deployment performance - Houstin, Aymeric; Paranhos Zitterbart, Daniel; Winterl, Alexander; Richter, Sebastian; Planas-Bielsa, Víctor; Chevallier, Damien; Ancel, André; Fournier, Jérôme; Fabry, Ben; Le Bohec, Céline (PLoS ONE, 2022)
An increasing number of marine animals are equipped with biologgers, to study their physiology, behaviour and ecology, often for conservation purposes. To minimise the impacts of biologgers on the animals' welfare, the Refinement principle from the Three Rs framework (Replacement, Reduction, Refinement) urges to continuously test and evaluate new and updated biologging protocols. Here, we propose alternative and promising techniques for emperor penguin (Aptenodytes forsteri) capture and on-site logger deployment that aim to mitigate the potential negative impacts of logger deployment on these birds. We equipped adult emperor penguins for short-term (GPS, Time-Depth Recorder (TDR)) and long-term (i.e. planned for one year) deployments (ARGOS platforms, TDR), as well as juvenile emperor penguins for long-term deployments (ARGOS platforms) in the Weddell Sea area where they had not yet been studied. We describe and qualitatively evaluate our protocols for the attachment of biologgers on-site at the colony, the capture of the animals and the recovery of the devices after deployment. We report unprecedented recaptures of long-term equipped adult emperor penguins (50% of equipped individuals recaptured after 290 days). Our data demonstrate that the traditional technique of long-term attachment by gluing the biologgers directly to the back feathers causes excessive feather breakage and the loss of the devices after a few months. We therefore propose an alternative method of attachment for back-mounted devices. This technique led to successful year-round deployments on 37.5% of the equipped juveniles. Finally, we also disclose the first deployments of leg-bracelet mounted TDRs on emperor penguins. Our findings highlight the importance of monitoring potential impacts of biologger deployments on the animals and the need to continue to improve methods to minimize disturbance and enhance performance and results.
CRIS-Team Scopus Importer:2022-08-12

Biomechanical characterization of a desminopathy in primary human myoblasts - Bonakdar, Navid; Luczak, Justyna; Lautscham, Lena; Czonstke, Maja; Koch, Thorsten M.; Mainka, Astrid; Jungbauer, Tajana; Goldmann, Wolfgang H.; Schroeder, Rolf; Fabry, Ben (Biochemical and Biophysical Research Communications, 2012)

Biomembrane-mimicking lipid bilayer system as a mechanically tunable cell substrate - Lautscham, Lena; Lin, Corey Y.; Auernheimer, Vera; Naumann, Christoph A.; Goldmann, Wolfgang; Fabry, Ben (Biomaterials, 2014)

Bioprinting and Differentiation of Adipose-Derived Stromal Cell Spheroids for a 3D Breast Cancer-Adipose Tissue Model - Horder, Hannes; Lasheras, Mar Guaza; Grummel, Nadine; Nadernezhad, Ali; Herbig, Johannes; Erguen, Sueleyman; Tessmar, Joerg; Groll, Juergen; Fabry, Ben; Bauer-Kreisel, Petra; Blunk, Torsten (Cells, 2021)
Biofabrication, including printing technologies, has emerged as a powerful approach to the design of disease models, such as in cancer research. In breast cancer, adipose tissue has been acknowledged as an important part of the tumor microenvironment favoring tumor progression. Therefore, in this study, a 3D-printed breast cancer model for facilitating investigations into cancer cell-adipocyte interaction was developed. First, we focused on the printability of human adipose-derived stromal cell (ASC) spheroids in an extrusion-based bioprinting setup and the adipogenic differentiation within printed spheroids into adipose microtissues. The printing process was optimized in terms of spheroid viability and homogeneous spheroid distribution in a hyaluronic acid-based bioink. Adipogenic differentiation after printing was demonstrated by lipid accumulation, expression of adipogenic marker genes, and an adipogenic ECM profile. Subsequently, a breast cancer cell (MDA-MB-231) compartment was printed onto the adipose tissue constructs. After nine days of co-culture, we observed a cancer cell-induced reduction of the lipid content and a remodeling of the ECM within the adipose tissues, with increased fibronectin, collagen I and collagen VI expression. Together, our data demonstrate that 3D-printed breast cancer-adipose tissue models can recapitulate important aspects of the complex cell-cell and cell-matrix interplay within the tumor-stroma microenvironment.
CRIS-Team WoS Importer:2021-05-14

Biphasic response of cell invasion to matrix stiffness in three-dimensional biopolymer networks - Lange, Nadine; Skodzek, Kai; Hurst, Sebastian; Mainka, Astrid; Steinwachs, Julian; Schneider, Julia; Aifantis, Katerina E.; Fabry, Ben (Acta Biomaterialia, 2015)

Breakdown of the Endothelial Barrier Function in Tumor Cell Transmigration - Mierke, Claudia; Paranhos Zitterbart, Daniel; Kollmannsberger, Philip; Raupach, Carina; Schlötzer-Schrehardt, Ursula; Goecke, Tamme W.; Behrens, Jürgen; Fabry, Ben (Biophysical Journal, 2007)
UnivIS-Import:2015-04-14:Pub.2007.nat.dphy.IAP.lpmt.breakd
Keywords: transendothelial migration; invasion; metastasis; endothelium; CXCR2; Gro-â; IL-8; cell mechanics

Breast Cancer Cells Adapt Contractile Forces to Overcome Steric Hindrance - Condor, Mar; Mark, Christoph; Gerum, Richard; Grummel, Nadine; Bauer, Andreas; Garcia-Aznar, Jose M.; Fabry, Ben (Biophysical Journal, 2019)
Cell migration through the extracellular matrix is governed by the interplay between cell-generated propulsion forces, adhesion forces, and resisting forces arising from the steric hindrance of the matrix. Steric hindrance in turn depends on matrix porosity, matrix deformability, cell size, and cell deformability. In this study, we investigate how cells respond to changes in steric hindrance that arise from altered cell mechanical properties. Specifically, we measure traction forces, cell morphology, and invasiveness of MDA-MB 231 breast cancer cells in three-dimensional collagen gels. To modulate cell mechanical properties, we either decrease nuclear deformability by twofold overexpression of the nuclear protein lamin A or we introduce into the cells stiff polystyrene beads with a diameter larger than the average matrix pore size. Despite this increase of steric hindrance, we find that cell invasion is only marginally inhibited, as measured by the fraction of motile cells and the mean invasion depth. To compensate for increased steric hindrance, cells employ two alternative strategies. Cells with higher nuclear stiffness increase their force polarity, whereas cells with large beads increase their net contractility. Under both conditions, the collagen matrix surrounding the cells stiffens dramatically and carries increased strain energy, suggesting that increased force polarity and increased net contractility are functionally equivalent strategies for overcoming an increased steric hindrance.
CRIS-Team WoS Importer:2019-04-18

Breathing pattern and additional work of breathing in spontaneously breathing patients with different ventilatory demands during inspiratory pressure support and automatic tube compensation - Fabry, Ben; et al. (Intensive Care Medicine, 1997)

Calcium supplementation of bioinks reduces shear stress-induced cell damage during bioprinting - Fischer, Lena; Nosratlo, Mojtaba; Hast, Katharina; Karakaya, Emine; Ströhlein, Nadi; Esser, Tilman; Gerum, Richard; Richter, Sebastian; Engel, Felix; Detsch, Rainer; Fabry, Ben; Thievessen, Ingo (Biofabrication, 2022)
During bioprinting, cells are suspended in a viscous bioink and extruded under pressure through small diameter printing needles. The combination of high pressure and small needle diameter exposes cells to considerable shear stress, which can lead to cell damage and death. Approaches to monitor and control shear stress-induced cell damage are currently not well established. To visualize the effects of printing-induced shear stress on plasma membrane integrity, we add FM 1-43 to the bioink, a styryl dye that becomes fluorescent when bound to lipid membranes, such as the cellular plasma membrane. Upon plasma membrane disruption, the dye enters the cell and also stains intracellular membranes. Extrusion of alginate-suspended NIH/3T3 cells through a 200 mu m printing needle led to an increased FM 1-43 incorporation at high pressure, demonstrating that typical shear stresses during bioprinting can transiently damage the plasma membrane. Cell imaging in a microfluidic channel confirmed that FM 1-43 incorporation is caused by cell strain. Notably, high printing pressure also impaired cell survival in bioprinting experiments. Using cell types of different stiffnesses, we find that shear stress-induced cell strain, FM 1-43 incorporation and cell death were reduced in stiffer compared to softer cell types and demonstrate that cell damage and death correlate with shear stress-induced cell deformation. Importantly, supplementation of the suspension medium with physiological concentrations of CaCl2 greatly reduced shear stress-induced cell damage and death but not cell deformation. As the sudden influx of calcium ions is known to induce rapid cellular vesicle exocytosis and subsequent actin polymerization in the cell cortex, we hypothesize that calcium supplementation facilitates the rapid resealing of plasma membrane damage sites. We recommend that bioinks should be routinely supplemented with physiological concentrations of calcium ions to reduce shear stress-induced cell damage and death during extrusion bioprinting.
CRIS-Team WoS Importer:2022-08-26

CameraTransform: A Python package for perspective corrections and image mapping - Gerum, Richard; Richter, Sebastian; Winterl, Alexander; Mark, Christoph; Fabry, Ben; Le Bohec, Céline; Paranhos Zitterbart, Daniel (SoftwareX, 2019)
Camera images and video recordings are simple and non-invasive tools to investigate animals in their natural habitat. Quantitative evaluations, however, often require an exact reconstruction of object positions, sizes, and distances in the image. Here, we provide an open source software package to perform such calculations. Our approach allows the user to correct for perspective distortion, transform images to “bird's-eye” view projections, or transform image-coordinates to real-world coordinates and vice versa. The extrinsic camera parameters that are necessary to perform such image corrections and transformations (elevation, tilt/roll angle, and heading of the camera) are obtained from the image using contextual information such as a visible horizon, GPS coordinates of landmarks, known object sizes, or images of the same object obtained from different viewing angles. All mathematical operations are implemented in the Python package CameraTransform. The performance of the implementation is evaluated using computer-generated synthetic images with known camera parameters. Moreover, we test our algorithm on images of emperor penguin colonies, and demonstrate that the camera tilt and roll angles can be estimated with an error of less than one degree, and the camera elevation with an error of less than 5%. The CameraTransform software package simplifies camera matrix-based image transformations and the extraction of quantitative image information. An extensive documentation and usage examples in an ecological context are provided at http://cameratransform.readthedocs.io.
CRIS-Team Scopus Importer:2019-10-08
Keywords: Camera lens distortions; Geo-referencing; Perspective projection; Quantitative image analysis

CameraTransform: a Scientific Python Package for Perspective Camera Corrections - Gerum, Richard; Richter, Sebastian; Winterl, Alexander; Fabry, Ben; Paranhos Zitterbart, Daniel (arXiv, 2017)

Cancer cell migration depends on adjacent ASC and adipose spheroids in a 3D bioprinted breast cancer model - Horder, Hannes; Böhringer, David; Endrizzi, Nadine; Hildebrand, Laura S.; Cianciosi, Alessandro; Stecher, Sabrina; Dusi, Franziska; Schweinitzer, Sophie; Watzling, Martin; Groll, Jürgen; Jüngst, Tomasz; Teßmar, Jörg; et al. (Biofabrication, 2024)
Breast cancer develops in close proximity to mammary adipose tissue and interactions with the local adipose environment have been shown to drive tumor progression. The specific role, however, of this complex tumor microenvironment in cancer cell migration still needs to be elucidated. Therefore, in this study, a 3D bioprinted breast cancer model was developed that allows for a comprehensive analysis of individual tumor cell migration parameters in dependence of adjacent adipose stroma. In this co-culture model, a breast cancer compartment with MDA-MB-231 breast cancer cells embedded in collagen is surrounded by an adipose tissue compartment consisting of adipose-derived stromal cell (ASC) or adipose spheroids in a printable bioink based on thiolated hyaluronic acid. Printing parameters were optimized for adipose spheroids to ensure viability and integrity of the fragile lipid-laden cells. Preservation of the adipogenic phenotype after printing was demonstrated by quantification of lipid content, expression of adipogenic marker genes, the presence of a coherent adipo-specific extracellular matrix, and cytokine secretion. The migration of tumor cells as a function of paracrine signaling of the surrounding adipose compartment was then analyzed using live-cell imaging. The presence of ASC or adipose spheroids substantially increased key migration parameters of MDA-MB-231 cells, namely motile fraction, persistence, invasion distance, and speed. These findings shed new light on the role of adipose tissue in cancer cell migration. They highlight the potential of our 3D printed breast cancer-stroma model to elucidate mechanisms of stroma-induced cancer cell migration and to serve as a screening platform for novel anti-cancer drugs targeting cancer cell dissemination.
CRIS-Team Scopus Importer:2024-07-12
Keywords: 3D bioprinting; adipose tissue; adipose-derived stromal cells; breast cancer model; live-cell imaging; migration; spheroids

CAS directly interacts with vinculin to control mechanosensing and focal adhesion dynamics - Janoštiak, Radoslav; Brabek, Jan; Auernheimer, Vera; Tatárová, Zuzana; Lautscham, Lena; Dey, Tuli; Gemperle, Jakub; Merkel, Rudolf; Goldmann, Wolfgang; Fabry, Ben; Rosel, Daniel (Cellular and Molecular Life Sciences, 2014)

CD24 induces localization of beta1 integrin to lipid raft domains - Runz, Steffen; Mierke, Claudia; Joumaa, Safwan; Behrens, Jürgen; Fabry, Ben; Altevogt, Peter (Biochemical and Biophysical Research Communications, 2008)

Cell Adhesion on Surface-Functionalized Magnesium - Wagener, Victoria; Schilling, Achim; Mainka, Astrid; Hennig, Diana; Gerum, Richard; Kelch, Marie-Luise; Keim, Simon; Fabry, Ben; Virtanen, Sannakaisa (ACS Applied Materials and Interfaces, 2016)
The biocompatibility of commercially pure magnesium-based (cp Mg) biodegradable implants is compromised of strong hydrogen evolution and surface alkalization due to high initial corrosion rates of cp Mg in the physiological environment. To mitigate this problem, the addition of corrosion-retarding alloying elements or coating of implant surfaces has been suggested. In the following work, we explored the effect of organic coatings on long-term cell growth. cp Mg was coated with aminopropyltriehtoxysilane + vitamin C (AV), carbonyldiimidazole (CDI), or stearic acid (SA). All three coatings have been previously suggested to reduce initial corrosion and to enhance protein adsorption and hence cell adhesion on magnesium surfaces. Endothelial cells (DH1+/+) and osteosarcoma cells (MG63) were cultured on coated samples for up to 20 days. To quantify Mg corrosion, electrochemical impedance spectroscopy (EIS) was measured after 1, 3, and 5 days of cell culture. We also investigated the speed of initial cell spreading after seeding using fluorescently labeled fibroblasts (NIH/3T3). Hydrogen evolution after contact with cell culture medium was markedly decreased on AV- and SA-coated Mg compared to uncoated Mg. These coatings also showed improved cell adhesion and spreading after 24 h of culture comparable to tissue-treated plastic surfaces. On AV-coated cp Mg, a confluent layer of endothelial cells formed after 5 days and remained intact for up to 20 days. Together, these data demonstrate that surface coating with AV is a viable strategy for improving long-term biocompatibility of cp Mg-based implants. EIS measurements confirmed that the presence of a confluent cell layer increased the corrosion resistance.
Keywords: cell adhesion; corrosion protection; impedance spectroscopy; magnesium; organic coating

Cell and tissue mechanics in cell migration - Lange, Janina; Fabry, Ben (Experimental Cell Research, 2013)

ClickPoints: an expandable toolbox for scientific image annotation and analysis - Gerum, Richard; Richter, Sebastian; Fabry, Ben; Paranhos Zitterbart, Daniel (Methods in Ecology and Evolution, 2016)

Clinorotation inhibits myotube formation by fluid motion, not by simulated microgravity - Mansour, Janet; Berwanger, Carolin; Jung, Marcel; Eichinger, Ludwig; Fabry, Ben; Clemen, Christoph S. (European Journal of Cell Biology, 2023)
To study processes related to weightlessness in ground-based cell biological research, a theoretically assumed microgravity environment is typically simulated using a clinostat – a small laboratory device that rotates cell culture vessels with the aim of averaging out the vector of gravitational forces. Here, we report that the rotational movement during fast clinorotation induces complex fluid motions in the cell culture vessel, which can trigger unintended cellular responses. Specifically, we demonstrate that suppression of myotube formation by 2D-clinorotation at 60 rpm is not an effect of the assumed microgravity but instead is a consequence of fluid motion. Therefore, cell biological results from fast clinorotation cannot be attributed to microgravity unless alternative explanations have been rigorously tested and ruled out. We consider two control experiments mandatory, i) a static, non-rotating control, and ii) a control for fluid motion. These control experiments are also highly recommended for other rotation speed settings and experimental conditions. Finally, we discuss strategies to minimize fluid motion in clinorotation experiments.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Clinostat; Fluid flow; Fluid motion; Gravity; Mammalian cell culture; Myoblasts; Myotubes; Shear stress; Simulated microgravity

Collective forces of tumor spheroids in three-dimensional biopolymer networks - Mark, Christoph; Grundy, Thomas J.; Strissel, Pamela; Böhringer, David; Grummel, Nadine; Gerum, Richard; Steinwachs, Julian; Hack, Carolin; Beckmann, Matthias; Eckstein, Markus; Strick, Reiner; O'Neill, Geraldine M.; et al. (eLife, 2020)
We describe a method for quantifying the contractile forces that tumor spheroids collectively exert on highly nonlinear three-dimensional collagen networks. While three-dimensional traction force microscopy for single cells in a nonlinear matrix is computationally complex due to the variable cell shape, here we exploit the spherical symmetry of tumor spheroids to derive a scale-invariant relationship between spheroid contractility and the surrounding matrix deformations. This relationship allows us to directly translate the magnitude of matrix deformations to the total contractility of arbitrarily sized spheroids. We show that our method is accurate up to strains of 50% and remains valid even for irregularly shaped tissue samples when considering only the deformations in the far field. Finally, we demonstrate that collective forces of tumor spheroids reflect the contractility of individual cells for up to 1 hr after seeding, while collective forces on longer timescales are guided by mechanical feedback from the extracellular matrix.
CRIS-Team WoS Importer:2020-05-22

Collective Synchronization of Contractile Forces in Tumor Spheroids - Böhringer, David; Mark, Christoph; Grummel, Nadine; Strissel, Pamela; Strick, Reiner; Grundy, Thomas J.; O'Neill, Geraldine M.; Fabry, Ben (BIOPHYSICAL JOURNAL, 2020)
CRIS-Team WoS Importer:2020-03-13

Continuous calculation of intratracheal pressure in tracheally intubated patients - Fabry, Ben; et al. (Anesthesiology, 1993)

Continuous calculation of intratracheal pressure in tracheally intubated patients - Fabry, Ben; et al. (Anesthesiology, 1993)

Contractile forces in tumor cell migration - Mierke, Claudia; Rosel, Daniel; Fabry, Ben; Brabek, Jan (European Journal of Cell Biology, 2008)

Correction: Collective forces of tumor spheroids in three-dimensional biopolymer networks. - Mark, Christoph; Grundy, Thomas J.; Strissel, Pamela; Böhringer, David; Grummel, Nadine; Gerum, Richard; Steinwachs, Julian; Hack, Carolin; Beckmann, Matthias; Eckstein, Markus; Strick, Reiner; O'Neill, Geraldine M.; et al. (eLife, 2020)
EVALuna2:417751

Corrosion of Mg alloy AZ91D in the presence of living cells - Virtanen, Sannakaisa; Seuß, Sigrid; Fabry, Ben; Turhan, Can Metehan; Seuß, Florian (Journal of Biomedical Materials Research Part B: Applied Biomaterials, 2011)

Cryopreservation impairs 3-D migration and cytotoxicity of natural killer cells - Mark, Christoph; Czerwinski, Tina; Roessner, Susanne; Mainka, Astrid; Hörsch, Franziska; Heublein, Lucas; Winterl, Alexander; Sanokowski, Sebastian; Richter, Sebastian; Bauer, Nina; Angelini, Thomas E.; Schuler, Gerold; et al. (Nature Communications, 2020)
Natural killer (NK) cells are important effector cells in the immune response to cancer. Clinical trials on adoptively transferred NK cells in patients with solid tumors, however, have thus far been unsuccessful. As NK cells need to pass stringent safety evaluation tests before clinical use, the cells are cryopreserved to bridge the necessary evaluation time. Standard degranulation and chromium release cytotoxicity assays confirm the ability of cryopreserved NK cells to kill target cells. Here, we report that tumor cells embedded in a 3-dimensional collagen gel, however, are killed by cryopreserved NK cells at a 5.6-fold lower rate compared to fresh NK cells. This difference is mainly caused by a 6-fold decrease in the fraction of motile NK cells after cryopreservation. These findings may explain the persistent failure of NK cell therapy in patients with solid tumors and highlight the crucial role of a 3-D environment for testing NK cell function.
CRIS-Team Scopus Importer:2020-10-23

Cryopreservation reduces the Ability to migrate and the Cytotoxicity of natural Killer Cells in 3D: Possible Effects on cellular Immunotherapy - Mark, Christoph; Czerwinksi, T.; Roessner, S.; Mainka, Astrid; Hoersch, F.; Heublein, L.; Winterl, Alexander; Sanokowski, Sebastian; Richter, S.; Bauer, N.; Angelini, T.; Schuler, Gerold; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-09-11

Cytoskeletal mechanics in adherent human airway smooth muscle cells: probe specificity and scaling of protein-protein dynamics - Puig-de-Morales, Marina; Millet, Emil J.; Fabry, Ben; Navajas, Daniel; Wang, Ning; Butler, James P.; Fredberg, Jeffrey (American Journal of Physiology-Cell Physiology, 2004)

Cytoskeletal remodeling and slow dynamics in the living cell - Bursac, Predrag; Lenormand, Guillaume; Fabry, Ben; Oliver, Madavi; Weitz, David A.; Viasnoff, Virgile; Butler, James P.; Fredberg, Jeffrey (Nature Materials, 2005)
Forced and spontaneous motions of microbeads tightly bound to the cytoskeleton (CSK) of human muscle cells were analyzed. HASM cells in passages 6-7 were serum-deprived for 24 h; serum deprivation arrests the cell cylce in the G1/G00 phases. It was observed that these spontaneous bead motions reflecting nanoscale CSK arrangements depended on both the approach to glass transition and energy release due to ATP hydrolysis. The results show that the trapping, intermittency, and approach to kinetic arrest are mesoscale features of CSK protein-protein interaction that link integrative phenotypic functions to the molecular event
UnivIS-Import:2015-03-09:Pub.2005.nat.dphy.IAP.lpmt.cytosk

Cytoskeletal remodelling and slow dynamics in the living cell - Bursac, Predrag; Lenormand, Guillaume; Fabry, Ben; Oliver, Madavi; Weitz, David A.; Viasnoff, Virgile; Butler, James P.; Fredberg, Jeffrey (Nature Materials, 2005)

Cytoskeleton dynamics: Fluctuations within the network - Bursac, Predrag; Fabry, Ben; Trepat, Xavier; Lenormand, Guillaume; Butler, James P.; Wang, Ning; Fredberg, Jeffrey; An, Steven S. (Biochemical and Biophysical Research Communications, 2007)

Cytoskletal mechanics in adherent human airway smooth muscle cells: probe specificity and scaling of protein-protein dynamics - Puig-de-Morales, Marina; Millet, Emil J.; Fabry, Ben; Navajas, Daniel; Wang, Ning; Butler, James P.; Fredberg, Jeffrey (American Journal of Physiology-Cell Physiology, 2004)
UnivIS-Import:2015-03-09:Pub.2004.nat.dphy.IAP.lpmt.cytosk

Delayed derecruitment after removal of PEEP in patients with acute lung injury - Fabry, Ben; et al. (Acta Anaesthesiologica Scandinavica, 1997)

DesR349P Mutation Results in Ultrastructural Disruptions and Compromise of Skeletal Muscle Biomechanics Already at Preclinical Stages in Young Mice before the Onset of Protein Aggregation - Diermeier, Stefanie; Haug, Michael; Reischl, Barbara; Buttgereit, Andreas; Schürmann, Sebastian; Spörrer, Marina; Goldmann, Wolfgang; Fabry, Ben; Elhimine, F.; Stehle, Robert; Pfitzer, Gabriele; Winter, L.; et al. (Elsevier (Cell Press) / Biophysical Society, 2016)
Mutations in the extra-sarcomeric protein desmin give rise to protein aggregate myopathies that interfere with cellular function. The R350P mutation is the most common human desminopathy. A murine DesR349P model of human DesR350P desminopathy was previously engineered. In this study, we followed the hypothesis of whether muscle cytoarchitecture and biomechanical properties are already altered in preclinical stages of R349P desminopathy. We applied non-linear second harmonic generation (SHG) and 2-photon fluorescence morphometry analysis to single fibres of fast- and slow-twitch muscle to analyze sarcomeric architecture and nuclear morphology. We found a vast disruption of the lateral sarcomere lattice (indicated by large ‘vernier’ densities) and myofibrillar angular deviations (indicated by cosine angle sums) in single DesR349P fibres. Homozygous fibres were more severely affected than heterozygous. The former showed a marked nuclear pathology with spheric nuclei, increased nuclear number and density. For biomechanics, we assessed active and passive properties. Axial stiffness of DesR349P muscle was much increased, both in fibre and myofibrillar homozygous bundles. Lateral stiffness of the membrane complex in myoblasts was increased in cells heterozygous for DesR349P while homozygous were similar to wt. Caffeine-induced force was compromised in heterozygous fibre bundles but increased in homozygous bundles. This was explained by a marked shift of myofibrillar Ca2+ sensitivity: heterozygous bundles being less sensitive but homozygous more sensitive to Ca2+. This points towards a specific compensatory mechanism in homozygous mutation to cope with otherwise compromised force production already at preclinical stages of desminopathy. Our findings provide a very first complete picture to explain compromised force in heterozygous DesR350P patients: increased muscle stiffness, higher susceptibility towards stretch-induced injury, disrupted myofibrillar alignment and compromised active force productio

Detecting long-range interactions between migrating cells - Metzner, C.; Hörsch, F.; Mark, Christoph; Czerwinski, Tina; Winterl, Alexander; Voskens, Caroline; Fabry, Ben (Scientific Reports, 2021)
Chemotaxis enables cells to systematically approach distant targets that emit a diffusible guiding substance. However, the visual observation of an encounter between a cell and a target does not necessarily indicate the presence of a chemotactic approach mechanism, as even a blindly migrating cell can come across a target by chance. To distinguish between the chemotactic approach and blind migration, we present an objective method that is based on the analysis of time-lapse recorded cell migration trajectories: For each movement step of a cell relative to the position of a potential target, we compute a p value that quantifies the likelihood of the movement direction under the null-hypothesis of blind migration. The resulting distribution of p values, pooled over all recorded cell trajectories, is then compared to an ensemble of reference distributions in which the positions of targets are randomized. First, we validate our method with simulated data, demonstrating that it reliably detects the presence or absence of remote cell-cell interactions. In a second step, we apply the method to data from three-dimensional collagen gels, interspersed with highly migratory natural killer (NK) cells that were derived from two different human donors. We find for one of the donors an attractive interaction between the NK cells, pointing to a cooperative behavior of these immune cells. When adding nearly stationary K562 tumor cells to the system, we find a repulsive interaction between K562 and NK cells for one of the donors. By contrast, we find attractive interactions between NK cells and an IL-15-secreting variant of K562 tumor cells. We therefore speculate that NK cells find wild-type tumor cells only by chance, but are programmed to leave a target quickly after a close encounter. We provide a freely available Python implementation of our p value method that can serve as a general tool for detecting long-range interactions in collective systems of self-driven agents.
CRIS-Team Scopus Importer:2021-08-06

Determining the mechanical properties of plectin in mouse myoblasts and keratinocytes - Bonakdar, Navid; Schilling, Achim; Spörrer, Marina; Lennert, Pablo; Mainka, Astrid; Winter, Lilli; Walko, Gernot; Wiche, Gerhard; Fabry, Ben; Goldmann, Wolfgang (Experimental Cell Research, 2015)
Plectin is the prototype of an intermediate filament (IF)-based cytolinker protein. It affects cells mechanically by interlinking and anchoring cytoskeletal filaments and acts as scaffolding and docking platform for signaling proteins to control cytoskeleton dynamics. The most common disease caused by mutations in the human plectin gene, epidermolysis bullosa simplex with muscular dystrophy (EBS-MD), is characterized by severe skin blistering and progressive muscular dystrophy. Therefore, we compared the biomechanical properties and the response to mechanical stress of murine plectin-deficient myoblasts and keratinocytes with wild-type cells. Using a cell stretching device, plectin-deficient myoblasts exhibited lower mechanical vulnerability upon external stress compared to wild-type cells, which we attributed to lower cellular pre-stress. Contrary to myoblasts, wild-type and plectin-deficient keratinocytes showed no significant differences. In magnetic tweezer measurements using fibronectin-coated paramagnetic beads, the stiffness of keratinocytes was higher than of myoblasts. Interestingly, cell stiffness, adhesion strength, and cytoskeletal dynamics were strikingly altered in plectin-deficient compared to wild-type myoblasts, whereas smaller differences were observed between plectin-deficient and wild-type keratinocytes, indicating that plectin might be more important for stabilizing cytoskeletal structures in myoblasts than in keratinocytes. Traction forces strongly correlated with the stiffness of plectin-deficient and wild-type myoblasts and keratinocytes. Contrary to that cell motility was comparable in plectin-deficient and wild-type myoblasts, but was significantly increased in plectin-deficient compared to wild-type keratinocytes. Thus, we postulate that the lack of plectin has divergent implications on biomechanical properties depending on the respective cell type.
EVALuna2:7284

Differential response of patient-derived primary glioblastoma cells to environmental stiffness - Grundy, Thomas James; De Leon, Ellen; Griffin, Kaitlyn Rose; Stringer, Brett William; Day, Bryan William; Fabry, Ben; Cooper-White, Justin; O'Neill, Geraldine Margarete (Scientific Reports, 2016)

Direct 3D‐Bioprinting of hiPSC‐derived Cardiomyocytes to Generate Functional Cardiac Tissues - Esser, Tilman; Anspach, Annalise; Muenzebrock, Katrin; Kah, Delf-Thorge Eric; Schrüfer, Stefan; Schenk, Joachim; Heinze, Katrin G.; Schubert, Dirk W.; Fabry, Ben; Engel, Felix (Advanced Materials, 2023)
3D-bioprinting is a promising technology to produce human tissues as drug screening tool or for organ repair. However, direct printing of living cells has proven difficult. Here, we present a method to directly 3D-bioprint human induced pluripotent stem cell (hiPSC)-derived cardiomyocytes embedded in a collagen-hyaluronic acid ink generating centimeter-sized functional ring- and ventricle-shaped cardiac tissues in an accurate and reproducible manner. The printed tissues contained hiPSC-derived cardiomyocytes with well-organized sarcomeres and exhibited spontaneous and regular contractions, which persisted for several months and were able to contract against passive resistance. Importantly, beating frequencies of the printed cardiac tissues could be modulated by pharmacological stimulation. This approach opens up new possibilities for generating complex functional cardiac tissues as models for advanced drug screening or as tissue grafts for organ repair or replacement.<br

Directionality of developing skeletal muscles is set by mechanical forces - Sunadome, Kazunori; Erickson, Alek G.; Kah, Delf-Thorge Eric; Fabry, Ben; Adori, Csaba; Kameneva, Polina; Faure, Louis; Kanatani, Shigeaki; Kaucka, Marketa; Dehnisch Ellström, Ivar; Tesarova, Marketa; Zikmund, Tomas; et al. (Nature Communications, 2023)
Formation of oriented myofibrils is a key event in musculoskeletal development. However, the mechanisms that drive myocyte orientation and fusion to control muscle directionality in adults remain enigmatic. Here, we demonstrate that the developing skeleton instructs the directional outgrowth of skeletal muscle and other soft tissues during limb and facial morphogenesis in zebrafish and mouse. Time-lapse live imaging reveals that during early craniofacial development, myoblasts condense into round clusters corresponding to future muscle groups. These clusters undergo oriented stretch and alignment during embryonic growth. Genetic perturbation of cartilage patterning or size disrupts the directionality and number of myofibrils in vivo. Laser ablation of musculoskeletal attachment points reveals tension imposed by cartilage expansion on the forming myofibers. Application of continuous tension using artificial attachment points, or stretchable membrane substrates, is sufficient to drive polarization of myocyte populations in vitro. Overall, this work outlines a biomechanical guidance mechanism that is potentially useful for engineering functional skeletal muscle.
CRIS-Team Scopus Importer:2023-07-07

Do biophysical properties of the airway smooth muscle in culture predict airway hyperresponsiveness? - An, Steven S.; Fabry, Ben; Trepat, Xavier; Wang, Ning; Fredberg, Jeffrey (American Journal of Respiratory Cell and Molecular Biology, 2006)

Dual-wavelength stopped-flow analysis of the lateral and longitudinal assembly kinetics of vimentin - Schween, Lovis; Mücke, Norbert; Portet, Stéphanie; Goldmann, Wolfgang; Herrmann, Harald; Fabry, Ben (Biophysical Journal, 2022)
Vimentin is a highly charged intermediate filament protein that inherently forms extended dimeric coiled coils, which serve as the basic building blocks of intermediate filaments. Under low ionic strength conditions, vimentin filaments dissociate into uniform tetrameric complexes of two anti-parallel-oriented, half-staggered coiled-coil dimers. By addition of salt, vimentin tetramers spontaneously reassemble into filaments in a time-dependent process: 1) lateral assembly of tetramers into unit-length filaments, 2) longitudinal annealing of unit-length filaments, and 3) longitudinal assembly of filaments coupled with subsequent radial compaction. To independently determine the lateral and longitudinal assembly kinetics, we measure with a stopped-flow instrument the static light scattering signal at two different wavelengths (405 and 594 nm) with a temporal resolution of 3 ms and analyze the signals based on Rayleigh-Gans theory. This theory considers that the intensity of the scattered light depends not only on the molecular weight of the scattering object but also on its shape. This shape dependence is more pronounced at shorter wavelengths, allowing us to decompose the scattered light signal into its components arising from lateral and longitudinal filament assembly. We demonstrate that both the lateral and longitudinal filament assembly kinetics increase with salt concentration.
CRIS-Team Scopus Importer:2022-10-21

Durotropic Growth of Pollen Tubes(1)([OPEN]) - Reimann, Ronny; Kah, Delf-Thorge Eric; Mark, Christoph; Dettmer, Jan; Reimann, Theresa; Gerum, Richard; Geitmann, Anja; Fabry, Ben; Dietrich, Petra; Kost, Benedikt (Plant Physiology, 2020)
To reach the female gametophyte, growing pollen tubes must penetrate different tissues within the pistil, the female reproductive organ of a flower. Past research has identified various chemotropic cues that guide pollen tubes through the transmitting tract of the pistil, which represents the longest segment of its growth path. In addition, physical mechanisms also play a role in pollen tube guidance; however, these processes remain poorly understood. Here we show that pollen tubes from plants with solid transmitting tracts actively respond to the stiffness of the environment. We found that pollen tubes fromNicotiana tabacumand other plant species with a solid or semisolid transmitting tract increase their growth rate in response to an increasing matrix stiffness. By contrast, pollen tubes fromLilium longiflorumand other plant species with a hollow transmitting tract decrease their growth rate with increasing matrix stiffness, even though the forces needed to maintain a constant growth rate remain far below the maximum penetration force these pollen tubes are able to generate. Moreover, when confronted with a transition from a softer to a stiffer matrix, pollen tubes fromN. tabacumdisplay a greater ability to penetrate into a stiffer matrix compared with pollen tubes fromL. longiflorum,even though the maximum force generated by pollen tubes fromN. tabacum(11 mu N) is smaller than the maximum force generated by pollen tubes fromL. longiflorum(36 mu N). These findings demonstrate a mechano-sensitive growth behavior, termed here durotropic growth, that is only expressed in pollen tubes from plants with a solid or semisolid transmitting tract and thus may contribute to an effective pollen tube guidance within the pistil.
CRIS-Team WoS Importer:2020-07-10

Durotropic Growth of Pollen Tubes - Reimann, Ronny; Kah, Delf-Thorge Eric; Mark, Christoph; Dettmer, Jan; Reimann, Theresa; Gerum, Richard; Geitmann, Anja; Fabry, Ben; Dietrich, Petra; Kost, Benedikt (Plant Physiology, 2020)
To reach the female gametophyte, growing pollen tubes must penetrate different tissues within the pistil, the female reproductive organ of a flower. Past research has identified various chemotropic cues that guide pollen tubes through the transmitting tract of the pistil, which represents the longest segment of its growth path. In addition, physical mechanisms also play a role in pollen tube guidance; however, these processes remain poorly understood. Here we show that pollen tubes from plants with solid transmitting tracts actively respond to the stiffness of the environment. We found that pollen tubes from Nicotiana tabacum and other plant species with a solid or semisolid transmitting tract increase their growth rate in response to an increasing matrix stiffness. By contrast, pollen tubes from Lilium longiflorum and other plant species with a hollow transmitting tract decrease their growth rate with increasing matrix stiffness, even though the forces needed to maintain a constant growth rate remain far below the maximum penetration force these pollen tubes are able to generate. Moreover, when confronted with a transition from a softer to a stiffer matrix, pollen tubes from N. tabacum display a greater ability to penetrate into a stiffer matrix compared with pollen tubes from L. longiflorum, even though the maximum force generated by pollen tubes from N. tabacum (11 µN) is smaller than the maximum force generated by pollen tubes from L. longiflorum (36 µN). These findings demonstrate a mechano-sensitive growth behavior, termed here durotropic growth, that is only expressed in pollen tubes from plants with a solid or semisolid transmitting tract and thus may contribute to an effective pollen tube guidance within the pistil. Animal sperm cells have the ability to freely swim by rhythmic movements of their flagella (Malo et al., 2006). By contrast, sperm cells of angiosperm plants have lost this ability (Dresselhaus et al., 2016) and are contained within the cytoplasm of the vegetative cell of a pollen grain. Upon germination, the vegetative pollen cell forms a long tubular protrusion, the pollen tube, which rapidly elongates through the pistil and transports the enclosed immobile sperm cells toward the egg cell and the central cell for double fertilization (Zhang et al., 2017). As opposed to cell division, pollen tubes elongate by tip growth. This process depends on a fine-tuned interplay between turgor pressure and vesicle trafficking, which delivers material required for cell wall and plasma membrane extension exclusively to the pollen tube tip (Lord, 2000; Chebli et al., 2013; Hafidh et al., 2016a; Grebnev et al., 2017; Luo et al., 2017). Therefore, only the surface at the pollen tube tip changes its relative position with respect to the environment during cell elongation, giving rise to a low-friction and thus energetically favorable growth process that has also been observed in other invasively growing cell types, such as root hairs, fungal hyphae, and neurons (Palanivelu and Preuss, 2000; Sanati Nezhad and Geitmann, 2013). This mechanism enables pollen tubes of some plant species to grow at rates of more than 300 µm·min−1 (Williams et al., 2016), faster than any other plant cell (Shamsudhin et al., 2016). To reach the female gametophyte, growing pollen tubes must penetrate different tissues within the pistil. After initial growth on the surface of the stigma, pollen tubes subsequently elongate through the transmitting tract within the style and the ovary, penetrate the septum epidermis to leave the transmitting tract, continue to elongate on the surface of the funiculus and through the micropyle of the ovule, and finally enter a synergid cell, where they burst and discharge their cytoplasm together with the enclosed sperm cells (Hulskamp et al., 1995; Crawford et al., 2007). Over the past two decades, many factors have been identified that are involved in the guidance of pollen tubes along their path toward the female gametophyte, including sugars, calcium ions, nitric oxide, lipids, and secreted peptides (Hulskamp et al., 1995; Ray et al., 1997; Wolters-Arts et al., 1998; Mollet et al., 2000; Higashiyama et al., 2003; Prado et al., 2004; Chae and Lord, 2011; Sanati Nezhad et al., 2014; Qu et al., 2015; Hafidh et al., 2016b; Higashiyama and Yang, 2017; Jiao et al., 2017). Most of these chemical signals guide the pollen tubes toward and inside the ovule following their emergence from the transmitting tract. However, the transmitting tract of the pistil typically represents the longest section of the pollen tube growth path in situ (de Graaf et al., 2003; Crawford and Yanofsky, 2008). Because chemical gradients are more difficult to maintain over longer distances, physical guidance mechanisms are thought to play an important role in directing pollen tube growth within the transmitting tract (Lennon et al., 1998; Lush et al., 2000), but this has so far not been characterized in detail. Flowers of different plant species display a highly diverse pistil and transmitting tract anatomy, which complicates the investigation of physical pollen tube guidance. Within the transmitting tract of hollow (sometimes called “open”) styles, as observed for example in Lilium longiflorum flowers, pollen tubes grow on the epidermal surface of a cell-free canal filled with a viscous extracellular matrix (Sanders and Lord, 1992; de Graaf et al., 2001; Erbar, 2003). By contrast, the transmitting tract in solid (sometimes called “closed”) styles, as found in Arabidopsis (Arabidopsis thaliana) and Nicotiana tabacum flowers, is filled with tissue composed of cells embedded in an extracellular matrix, which pollen tubes need to penetrate (Lennon et al., 1998; Cheung et al., 2000; Erbar, 2003). The tissue within the transmitting tract imposes a substantial physical resistance on pollen tube growth (Agudelo et al., 2012), in particular as intercellular spaces in this tissue are typically smaller than the pollen tube diameter (Lennon et al., 1998; Roy et al., 1999; Cheung et al., 2000). The maximum (or stalling) force that a growing pollen tube can generate to overcome the mechanical resistance restricting its expansion within pistil tissues is determined by the product of the hydrostatic turgor pressure and the cross-sectional area of the tube at its tip. Maximum forces generated by L. longiflorum tubes measured with capacitive force sensors (Burri et al., 2018) were found to be in the range of 9.6 ± 1.6 µN, whereas forces generated by Camellia japonica pollen tubes measured with soft microcantilevers (Ghanbari et al., 2018) were found to be around 1.5 µN. However, direct force measurements using capacitive force sensors or microcantilevers are technically highly demanding (Agudelo et al., 2013; Ghanbari et al., 2014; Sanati Nezhad et al., 2014). Moreover, measurements of the maximum stalling force cannot provide information on the penetration force of a pollen tube growing inside a pistil under physiological conditions, as this force depends on the growth rate and the mechanical impedance of the surrounding matrix (Sanati Nezhad et al., 2013). In this study, we present a method to estimate the penetration force generated by a pollen tube tip during its growth through matrices of different stiffness. With this method, we investigated pollen tubes from plant species, both with hollow and with solid styles, and measured the relationship between penetration force and growth rate for matrices with different mechanical properties. We found that pollen tubes from plants with solid styles, but not those from plants with hollow styles, increase their growth rate in matrices with higher physical resistance, indicating that an active mechanosensory mechanism controls the tropic growth of these pollen tubes, which may help them to navigate through the complex architecture of the pistil to reach the female gametophyte. We propose the term durotropism for this mechanosensory mechanism that guides pollen tubes from plants with solid styles toward stiffer environments, analogous to the term durotaxis that describes the preferential migration of mammalian mesenchymal cells toward regions with higher substrate rigidity (Lo et al., 2000

Dynamic delay time compensation for sampling capillaries used in respiratory mass spectrometry - Eberhard, Luc; Haberthür, Christoph; Fabry, Ben; Guttmann, Josef (Technology and Health Care, 1999)

Dynamic equilibration of airway smooth muscle contraction during physiological loading - Latourelle, Jeanne; Fabry, Ben; Fredberg, Jeffrey (Journal of Applied Physiology, 2002)

Dynamic traction force measurements of migrating immune cells in 3D biopolymer matrices - Böhringer, David; Cóndor, Mar; Bischof, Lars; Czerwinski, Tina; Gampl, Niklas; Ngo, Phuong; Bauer, Andreas; Bosch-Voskens, Caroline; Lopez Posadas, Rocío; Franze, Kristian; Budday, Silvia; Mark, Christoph; et al. (Nature Physics, 2024)
Immune cells, such as natural killer cells, migrate with high speeds of several micrometres per minute through dense tissue. However, the magnitude of the traction forces during this migration is unknown. Here we present a method to measure dynamic traction forces of fast migrating cells in biopolymer matrices from the observed matrix deformations. Our method accounts for the mechanical nonlinearity of the three-dimensional tissue matrix and can be applied to time series of confocal or bright-field image stacks. It allows for precise force reconstruction over a wide range of force magnitudes and object sizes—even when the imaged volume captures only a small part of the matrix deformation field. We demonstrate the broad applicability of our method by measuring forces from around 1 nN for axon growth cones up to around 10 μN for mouse intestinal organoids. We find that natural killer cells show bursts of large traction forces around 50 nN that increase with matrix stiffness. These force bursts are driven by myosin II contractility, mediated by integrin β1 adhesions, focal adhesion kinase and Rho-kinase activity, and occur predominantly when the cells migrate through narrow matrix pores.
CRIS-Team Scopus Importer:2024-11-29

Early signs of architectural and biomechanical failure in isolated myofibers and immortalized myoblasts from desmin-mutant knock-in mice - Diermeier, Stefanie; Iberl, Julian; Vetter, Karoline; Haug, Michael; Pollmann, Charlotte; Reischl, Barbara; Buttgereit, Andreas; Schürmann, Sebastian; Spörrer, Marina; Goldmann, Wolfgang; Fabry, Ben; Elhamine, Fatiha; et al. (Scientific Reports, 2017)
In striated muscle, desmin intermediate filaments interlink the contractile myofibrillar apparatus with mitochondria, nuclei, and the sarcolemma. The desmin network's pivotal role in myocytes is evident since mutations in the human desmin gene cause severe myopathies and cardiomyopathies. Here, we investigated skeletal muscle pathology in myofibers and myofibrils isolated from young hetero- and homozygous R349P desmin knock-in mice, which carry the orthologue of the most frequent human desmin missense mutation R350P. We demonstrate that mutant desmin alters myofibrillar cytoarchitecture, markedly disrupts the lateral sarcomere lattice and distorts myofibrillar angular axial orientation. Biomechanical assessment revealed a high predisposition to stretch-induced damage in fiber bundles of R349P mice. Notably, Ca(2)(+)-sensitivity and passive myofibrillar tension were decreased in heterozygous fiber bundles, but increased in homozygous fiber bundles compared to wildtype mice. In a parallel approach, we generated and subsequently subjected immortalized heterozygous R349P desmin knock-in myoblasts to magnetic tweezer experiments that revealed a significantly increased sarcolemmal lateral stiffness. Our data suggest that mutated desmin already markedly impedes myocyte structure and function at pre-symptomatic stages of myofibrillar myopathies.
EVALuna2:7360

Effects of mechanical unloading/loading on respiratory loop gain and periodic breathing in man - Haberthür, Christoph; Fabry, Ben; Zappe, Detlef; Guttmann, Josef (RESP PHYSIOL, 1998)

Emergence of Asynchronous Local Clocks in Excitable Media - Gerum, Richard; Fabry, Ben; Metzner, Claus (PLoS ONE, 2015)

Epithelial RAC1-dependent cytoskeleton dynamics controls cell mechanics, cell shedding and barrier integrity in intestinal inflammation - Martínez Sánchez, Luz del Carmen; Phuong Anh Ngo; Pradhan, Rashmita; Becker, Lukas S; Böhringer, David; Soteriou, Despina; Kubankova, Marketa; Schweitzer, Christine; Koch, Tatyana; Thonn, Veronika; Erkert, Lena; Stolzer, Iris; et al. (Gut, 2022)
Objective Increased apoptotic shedding has been linked to intestinal barrier dysfunction and development of inflammatory bowel diseases (IBD). In contrast, physiological cell shedding allows the renewal of the epithelial monolayer without compromising the barrier function. Here, we investigated the role of live cell extrusion in epithelial barrier alterations in IBD. Design Taking advantage of conditional GGTase and RAC1 knockout mice in intestinal epithelial cells (Pggt1b (i Delta IEC) and Rac1 (i Delta IEC) mice), intravital microscopy, immunostaining, mechanobiology, organoid techniques and RNA sequencing, we analysed cell shedding alterations within the intestinal epithelium. Moreover, we examined human gut tissue and intestinal organoids from patients with IBD for cell shedding alterations and RAC1 function. Results Epithelial Pggt1b deletion led to cytoskeleton rearrangement and tight junction redistribution, causing cell overcrowding due to arresting of cell shedding that finally resulted in epithelial leakage and spontaneous mucosal inflammation in the small and to a lesser extent in the large intestine. Both in vivo and in vitro studies (knockout mice, organoids) identified RAC1 as a GGTase target critically involved in prenylation-dependent cytoskeleton dynamics, cell mechanics and epithelial cell shedding. Moreover, inflamed areas of gut tissue from patients with IBD exhibited funnel-like structures, signs of arrested cell shedding and impaired RAC1 function. RAC1 inhibition in human intestinal organoids caused actin alterations compatible with arresting of cell shedding. Conclusion Impaired epithelial RAC1 function causes cell overcrowding and epithelial leakage thus inducing chronic intestinal inflammation. Epithelial RAC1 emerges as key regulator of cytoskeletal dynamics, cell mechanics and intestinal cell shedding. Modulation of RAC1 might be exploited for restoration of epithelial integrity in the gut of patients with IBD.
CRIS-Team WoS Importer:2022-03-25

Ergebnisse der Sicca-Forschungsförderung 2016 - Musayeva, A; Gericke, A; Jäger, Franziska; Paulsen, Friedrich; Braun, M; Fabry, Ben; Braun, R; Pauly, Diana; Holtmann, C; Geerling, Gerd; Goldblum, David; Horwath-Winter, Jutta; et al. (Ophthalmologe, 2020)
The Sicca-Förderpreis (Dry Eye Award) supports the development of scientific research on the pathogenesis, diagnostics, and treatment of dry eye and ocular surface diseases. It is awarded after a limited call for proposals in German-speaking countries, written application and selection of the award winner after evaluation by a jury of ophthalmologists working in basic and clinical science. In this article examples of the results of funded projects of the Sicca-Förderpreis 2016 are cursorily described, which were presented at the Ophthalmological Academy of Germany 2019 (Augenärztliche Akademie Deutschland 2019) and therefore provide an insight into current scientific developments. The role of muscarinic receptors and those of urea in the pathogenesis of dry eye as well as the (missing) correlation of tear film stability, viscosity and surface tension are highlighted. A project on the early detection of ocular involvement in graft versus host disease and the idea of treating meibomian gland dysfunction with eyelid surgery techniques are also groundbreaking. The outlined projects represent the potential for further substantial developments in the understanding, diagnostics and treatment of dry eye; however, their long-term clinical relevance still needs to be established.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Eyelid tension; Graft versus host disease; Muscarinic receptor; Tear film stability; Urea

Estimating the 3D pore size distribution of biopolymer networks from directionally biased data. - Lang, Nadine; Münster, Stefan; Metzner, Claus; Krauß, Patrick; Schürmann, Sebastian; Lange, Janina; Aifantis, Katerina E.; Friedrich, Oliver; Fabry, Ben (Biophysical Journal, 2013)
The pore size of biopolymer networks governs their mechanical properties and strongly impacts the behavior of embedded cells. Confocal reflection microscopy and second harmonic generation microscopy are widely used to image biopolymer networks; however, both techniques fail to resolve vertically oriented fibers. Here, we describe how such directionally biased data can be used to estimate the network pore size. We first determine the distribution of distances from random points in the fluid phase to the nearest fiber. This distribution follows a Rayleigh distribution, regardless of isotropy and data bias, and is fully described by a single parameter–the characteristic pore size of the network. The bias of the pore size estimate due to the missing fibers can be corrected by multiplication with the square root of the visible network fraction. We experimentally verify the validity of this approach by comparing our estimates with data obtained using confocal fluorescence microscopy, which represents the full structure of the network. As an important application, we investigate the pore size dependence of collagen and fibrin networks on protein concentration. We find that the pore size decreases with the square root of the concentration, consistent with a total fiber length that scales linearly with concentration.

Ex vivo expanded NK Cells from Melanoma Patients receive their Migration in a 3D Model and lyse autologous Melanoma Cells - Rossner, S.; Czerwinski, Tina; Mark, Christoph; Gross, S.; Karg, Margarete; Bosch, Jacobus J.; Schuler-Thurner, Beatrice; Fabry, Ben; Schuler, Gerold; Bosch-Voskens, C. (2018)
EVALuna2:34775

Fast phenotyping of monocytes mechanics under the cytokine storm - Eroles, Mar; Gerum, Richard; Fabry, Ben; Rico, Felix (EUROPEAN BIOPHYSICS JOURNAL WITH BIOPHYSICS LETTERS, 2021)
CRIS-Team WoS Importer:2021-08-13

Fiber alignment in 3D collagen networks as a biophysical marker for cell contractility - Böhringer, David; Bauer, Andreas; Moravec, Ivana; Bischof, Lars; Kah, Delf-Thorge Eric; Mark, Christoph; Grundy, Thomas J.; Görlach, Ekkehard; O'Neill, Geraldine M.; Budday, Silvia; Strissel, Pamela; Strick, Reiner; et al. (Matrix Biology, 2023)
Cells cultured in 3D fibrous biopolymer matrices exert traction forces on their environment that induce deformations and remodeling of the fiber network. By measuring these deformations, the traction forces can be reconstructed if the mechanical properties of the matrix and the force-free matrix configuration are known. These requirements limit the applicability of traction force reconstruction in practice. In this study, we test whether force-induced matrix remodeling can instead be used as a proxy for cellular traction forces. We measure the traction forces of hepatic stellate cells and different glioblastoma cell lines and quantify matrix remodeling by measuring the fiber orientation and fiber density around these cells. In agreement with simulated fiber networks, we demonstrate that changes in local fiber orientation and density are directly related to cell forces. By resolving Rho-kinase (ROCK) inhibitor-induced changes of traction forces, fiber alignment, and fiber density in hepatic stellate cells, we show that the method is suitable for drug screening assays. We conclude that differences in local fiber orientation and density, which are easily measurable, can be used as a qualitative proxy for changes in traction forces. The method is available as an open-source Python package with a graphical user interface.
CRIS-Team Scopus Importer:2023-12-22
Keywords: Biopolymer Networks; Fiber Orientation; Mechanobiology; Traction Force Microscopy

Fibrous protein-based hydrogels for cell encapsulation - Silva, Raquel; Fabry, Ben; Boccaccini, Aldo R. (Biomaterials, 2014)
Tissue scaffolds play a vital role in tissue engineering by providing a native tissue-mimicking environment for cells, with the aim to promote cell proliferation, proper cell differentiation, and regeneration. To better mimic the microenvironment of native tissues, novel techniques and materials have emerged in recent years. Among them, hydrogels formed from self-assembled biopolymer networks are particularly interesting. This paper reviews the fabrication and use of fibrous protein-based hydrogels, with an emphasis on silk, keratin elastin and resilin proteins. Hydrogels formed by these proteins show close structural, chemical and mechanical similarities with the extracellular matrix, typically good biological compatibility, and they can trigger specific cellular responses. In addition, these hydrogels can be degraded in the body by proteolytic enzymes. For these reasons, fibrous protein hydrogels are one of the most versatile materials for tissue engineering. © 2014 Elsevier Ltd.
Keywords: Biomaterials; Cell-encapsulation; Fibrous-proteins; Hydrogels

Filamin A is essential for active cell stiffening but not passive stiffening under external force - Kaszar, Karen E.; Nakamura, Fumihiko; Hu, Shaohua; Kollmannsberger, Philip; Fabry, Ben; Stossel, Thomas Peter; Wang, Ning; Weitz, David A. (Journal of Biophysics, 2009)

Filamin A is essential for active cell stiffening but not passive stiffening under external force - Kaszar, Karen E.; Nakamura, Fumihiko; Hu, Shaohua; Kollmannsberger, Philip; Fabry, Ben; Stossel, Thomas Peter; Wang, Ning; Weitz, David A. (Journal of Biophysics, 2009)

Flow and hydrodynamic shear stress inside a printing needle during biofabrication - Müller, Sebastian J.; Mirzahossein, Elham; Iftekhar, Emil N.; Bächer, Christian; Schrüfer, Stefan; Schubert, Dirk W.; Fabry, Ben; Gekle, Stephan (PLoS ONE, 2020)
We present a simple but accurate algorithm to calculate the flow and shear rate profile of shear thinning fluids, as typically used in biofabrication applications, with an arbitrary viscosity-shear rate relationship in a cylindrical nozzle. By interpolating the viscosity with a set of power-law functions, we obtain a mathematically exact piecewise solution to the incompressible Navier-Stokes equation. The algorithm is validated with known solutions for a simplified Carreau-Yasuda fluid, full numerical simulations for a realistic chitosan hydrogel as well as experimental velocity profiles of alginate and chitosan solutions in a microfluidic channel. We implement the algorithm in an easy-to-use Python tool, included as Supplementary Material, to calculate the velocity and shear rate profile during the printing process, depending on the shear thinning behavior of the bioink and printing parameters such as pressure and nozzle size. We confirm that the shear stress varies in an exactly linear fashion, starting from zero at the nozzle center to the maximum shear stress at the wall, independent of the shear thinning properties of the bioink. Finally, we demonstrate how our method can be inverted to obtain rheological bioink parameters in-situ directly before or even during printing from experimentally measured flow rate versus pressure data.
CRIS-Team Scopus Importer:2020-08-07

Fluctuations of cytoskeleton-bound microbeads - the effect of bead-receptor binding dynamics - Metzner, Claus; Raupach, Carina; Mierke, Claudia; Fabry, Ben (Journal of Physics: Condensed Matter, 2010)

Focal Adhesion Kinase Stabilizes the Cytoskeleton - Fabry, Ben; Klemm, Anna; Kienle, Sandra; Schäffer, Tilman; Goldmann, Wolfgang (Journal of Biophysics, 2011)

Fractional derivatives embody essential features of cell rheological behavior - Fabry, Ben; et al. (Annals of Biomedical Engineering, 2003)

Head/tail interaction of vinculin influences cell mechanical behavior - Diez, Gerold; Auernheimer, Vera; Fabry, Ben; Goldmann, Wolfgang (Biochemical and Biophysical Research Communications, 2011)

High-Force Magnetic Tweezers with Force Feedback for Biological Applications - Kollmannsberger, Philip; Fabry, Ben (Review of Scientific Instruments, 2007)

High-Force Magnetic Tweezers with Hysteresis-Free Force Feedback - Kah, Delf-Thorge Eric; Dürrbeck, Christopher; Schneider, Werner; Fabry, Ben; Gerum, Richard (Biophysical Journal, 2020)
Magnetic tweezers based on a solenoid with an iron alloy core are widely used to apply large forces (∼100 nN) onto micron-sized (∼5 μm) superparamagnetic particles for mechanical manipulation or microrheological measurements at the cellular and molecular level. The precision of magnetic tweezers, however, is limited by the magnetic hysteresis of the core material, especially for time-varying force protocols. Here, we eliminate magnetic hysteresis by a feedback control of the magnetic induction, which we measure with a Hall sensor mounted to the distal end of the solenoid core. We find that the generated force depends on the induction according to a power-law relationship and on the bead-tip distance according to a stretched exponential relationship. Combined, they describe with only three parameters the induction-force-distance relationship, enabling accurate force calibration and force feedback. We apply our method to measure the force dependence of the viscoelastic and plastic properties of fibroblasts using a protocol with stepwise increasing and decreasing forces. We group the measured cells in a soft and a stiff cohort and find that softer cells show an increasing stiffness but decreasing plasticity with higher forces, indicating a pronounced stress stiffening of the cytoskeleton. By contrast, stiffer cells show no stress stiffening but an increasing plasticity with higher forces. These findings indicate profound differences between soft and stiff cells regarding their protection mechanisms against external mechanical stress. In summary, our method increases the precision, simplifies the handling, and extends the applicability of magnetic tweezers.
CRIS-Team Scopus Importer:2020-06-23

How to minimize mechanical power during controlled mechanical ventilation - Fabry, Ben (Intensive Care Medicine Experimental, 2024)
High intrapulmonary pressures, large tidal volumes, and elevated respiratory rates during controlled mechanical ventilation can lead to barotrauma, volutrauma, and atelectrauma. Mechanical power—defined as the product of the pressure–volume integral and respiratory rate—consolidates these three risk factors into a single, intuitive parameter. Several studies have demonstrated that higher mechanical power correlates with an increased risk of lung injury and mortality, prompting the suggestion that mechanical power should be minimized. However, under the constraint of maintaining a fixed alveolar minute ventilation and positive end-expiratory pressure (PEEP), it remains unclear how to adjust respiratory rate and tidal volume to minimize mechanical power. This study provides an analytical solution to this optimization problem. Accordingly, only the elastic component of mechanical power should be targeted for minimization. Regardless of lung elastance or resistance, or the mode and settings of the ventilator, the elastic power is minimized at a tidal volume equal to twice the anatomic dead space, or approximately 4.4 ml/kg of body weight.
CRIS-Team Scopus Importer:2025-02-04

Hydrodynamic thickening of lubricating fluid layer beneath sliding mesothelial tissues - Lin, Judy L.; Moghani, Taraneh; Fabry, Ben; Butler, James P.; Loring, Steven H. (Journal of Biomechanics, 2008)

Identification of DAPK as a scaffold protein for the LIMK/cofilin complex in TNF-induced apoptosis - Ivanovska, Jelena; Tregubova, Alexandra; Mahadevan, Vijayalakshmi; Chakilam, Saritha; Gandesiri, Muktheshwar; Benderska, Natalya; Ettle, Benjamin; Hartmann, Arndt; Söder, Stephan; Ziesche, Elisabeth; Fischer, Thomas; Lautscham, Lena; et al. (International Journal of Biochemistry and Cell Biology, 2013)
The role of cytoskeleton-associated proteins during TNF-induced apoptosis is not fully understood. A potential candidate kinase that might connect TNF signalling to actin reorganization is the death-associated protein kinase (DAPK). To identify new DAPK interaction partners in TNF-induced apoptosis, we performed a peptide array screen. We show that TNF-treatment enhanced the phosphorylation of LIMK at threonine508 and its downstream target cofilin at serine3 (p-cofilin(Ser3)). Modulation of DAPK activity and expression by DAPK inhibitor treatment, siRNA knockdown, and overexpression affected the phosphorylation of both proteins. We propose a 3D structural model where DAPK functions as a scaffold for the LIMK/cofilin complex and triggers a closer interaction of both proteins under TNF stimulation. Upon TNF a striking redistribution of LIMK, DAPK, and cofilin to the perinuclear compartment was observed. The pro-apoptotic DAPK/LIMK/cofilin multiprotein complex was abrogated in detached cells, indicating that its signaling was no longer needed if cells committed to apoptosis. P-cofilin(Ser3) was strongly accumulated in cells with condensed chromatin, pronounced membrane blebs and Annexin V up-regulation. From studying different cofilin(Ser3) mutants we suggest that p-cofilin(Ser3) is an indicator of TNF-induced apoptosis. Collectively, our findings identify a novel molecular cytoskeleton-associated mechanism in TNF-induced DAPK-dependent apoptosis.

Imaging localized neuronal activity at fast time scales through biomechanics - Patz, Samuel; Fovargue, Daniel; Schregel, Katharina; Nazari, Navid; Palotai, Miklos; Barbone, Paul E.; Fabry, Ben; Hammers, Alexander; Holm, Sverre; Kozerke, Sebastian; Nordsletten, David; Sinkus, Ralph (Science Advances, 2019)
Mapping neuronal activity noninvasively is a key requirement for in vivo human neuroscience. Traditional functional magnetic resonance (MR) imaging, with a temporal response of seconds, cannot measure high-level cognitive processes evolving in tens of milliseconds. To advance neuroscience, imaging of fast neuronal processes is required. Here, we show in vivo imaging of fast neuronal processes at 100-ms time scales by quantifying brain biomechanics noninvasively with MR elastography. We show brain stiffness changes of ∼10% in response to repetitive electric stimulation of a mouse hind paw over two orders of frequency from 0.1 to 10 Hz. We demonstrate in mice that regional patterns of stiffness modulation are synchronous with stimulus switching and evolve with frequency. For very fast stimuli (100 ms), mechanical changes are mainly located in the thalamus, the relay location for afferent cortical input. Our results demonstrate a new methodology for noninvasively tracking brain functional activity at high speed.
CRIS-Team Scopus Importer:2019-05-02

Imaging viscoelastic properties of living cells by AFM: Power-law rheology on the nanoscale - Hecht, Fabian M.; Rheinlaender, Johannes; Schierbaum, NIcolas; Goldmann, Wolfgang; Fabry, Ben; Schaeffer, Tilman E. (Soft Matter, 2015)

Implications of heterogeneous bead behavior on cell mechanical properties measured with magnetic twisting cytometry - Fabry, Ben; Maksym, Geoffrey N.; Hubmayr, Rolf; Butler, James P.; Fredberg, Jeffrey (Journal of Magnetism and Magnetic Materials, 1999)

Increased Motility and Suppression of Ex Vivo–Expanded Regulatory T Cells Designed for Adoptive Transfer Therapy in Ulcerative Colitis - Müller, Tanja; Liu, Lijuan; Czerwinski, Tina; Wiesinger, Manuel; Dedden, Mark; Paap, Eva-Maria; Ullrich, Karen; Atreya, Imke; Siegmund, Britta; Atreya, Raja; Fabry, Ben; Berking, Carola; et al. (Cellular and Molecular Gastroenterology and Hepatology, 2023)
CRIS-Team Scopus Importer:2023-06-02

Inhibition of Rho kinases increases directional motility of microvascular endothelial cells - Breyer, Johannes; Samarin, Jana; Rehm, Margot; Lautscham, Lena; Fabry, Ben; Goppelt-Strübe, Margarete (Biochemical Pharmacology, 2012)

Intracellular Drug Delivery with Anodic Titanium Dioxide Nanotubes and Nanocylinders - Hasanzadeh Kafshgari, Morteza; Mazare, Anca Valentina; Distaso, Monica; Goldmann, Wolfgang; Peukert, Wolfgang; Fabry, Ben; Schmuki, Patrik (ACS Applied Materials and Interfaces, 2019)
Titanium dioxide (TiO 2 ) holds remarkable promises for developing current theranostic strategies. Anodic TiO 2 nanostructures as a porous scaffold have offered a broad range of useful theranostic properties; however, previous attempts to generate single and uniform TiO 2 one-dimensional nanocarriers from anodic nanotube arrays have resulted in a broad cluster size distribution of arbitrarily broken tubes that are unsuitable for therapeutic delivery systems due to poor biodistribution and the risk of introducing tissue inflammation. Here, we achieve well-separated, uniformly shaped anodic TiO 2 nanotubes and nanocylinders through a time-varying electrochemical anodization protocol that leads to the generation of planar sheets of weakly connected nanotubes with a defined fracture point near the base. Subsequent sonication cleanly detaches the nanotubes from the base. Depending on the position of the fracture point, we can fabricate single-anodic nanocylinders that are open on both ends and nanotubes that are closed on one end. We proceed to show that anodic nanotubes and nanocylinders are nontoxic at therapeutic concentrations. When conjugated with the anticancer drug doxorubicin using a pH-responsive linker, they are readily internalized by cells and subsequently release their drug cargo into acidic intracellular compartments. Our results demonstrate that uniformly sized anodic TiO 2 nanotubes and nanocylinders are suitable for subcellular delivery of therapeutic agents in cancer therapy.
CRIS-Team Scopus Importer:2019-05-09
Keywords: electrochemical anodization; intracellular drug delivery; nanocylinders; nanotubes; titanium dioxide

Intracellular stress tomography reveals stress focusing and structural anisotropy in cytoskeleton of living cells - Hu, Shaohua; chen, jianxin; Fabry, Ben; Numaguchi, Yashushi; Gouldstone, Andrew; Ingber, Donald E.; Fredberg, Jeffrey; Butler, James P.; Wang, Ning (American journal of physiology. Cell physiology, 2003)

Intracellular stress tomography reveals stress focusing and structural anisotropy in cytoskeleton of living cells - Hu, Shaohua; chen, jianxin; Fabry, Ben; Numaguchi, Yashushi; Gouldstone, Andrew; Ingber, Donald E.; Fredberg, Jeffrey; Butler, James P.; Wang, Ning (American Journal of Physiology-Cell Physiology, 2003)

Intracellular stress tomography reveals stress focusing - Hu, Shaohua; chen, jianxin; Fabry, Ben; Numaguchi, Yashushi; Gouldstone, Andrew; Ingber, Donald E.; Fredberg, Jeffrey; Butler, James P.; Wang, Ning (American Journal of Physiology-Cell Physiology, 2003)
UnivIS-Import:2015-03-09:Pub.2003.nat.dphy.IAP.lpmt.intrac

In-Vivo Imaging of Cell Migration Using Contrast Enhanced MRI and SVM Based Post-Processing - Weis, Christian; Heß, Andreas; Budinsky, Lubos; Fabry, Ben (PLoS ONE, 2015)

Juvenile emperor penguin range calls for extended conservation measures in the Southern Ocean - Houstin, Aymeric; Paranhos Zitterbart, Daniel; Heerah, Karine; Eisen, Olaf; Planas-Bielsa, Victor; Fabry, Ben; Le Bohec, Celine (Royal Society Open Science, 2022)
To protect the unique and rich biodiversity of the Southern Ocean, conservation measures such as marine protected areas (MPAs) have been implemented. Currently, the establishment of several additional protection zones is being considered based on the known habitat distributions of key species of the ecosystems including emperor penguins and other marine top predators. However, the distribution of such species at sea is often insufficiently sampled. Specifically, current distribution models focus on the habitat range of adult animals and neglect that immatures and juveniles can inhabit different areas. By tracking eight juvenile emperor penguins in the Weddell Sea over 1 year and performing a meta-analysis including previously known data from other colonies, we show that conservation efforts in the Southern Ocean are insufficient for protecting this highly mobile species, and particularly its juveniles. We find that juveniles spend approximately 90% of their time outside the boundaries of proposed and existing MPAs, and that their distribution extends beyond (greater than 1500 km) the species' extent of occurrence as defined by the International Union for Conservation of Nature. Our data exemplify that strategic conservation plans for the emperor penguin and other long-lived ecologically important species should consider the dynamic habitat range of all age classes.
CRIS-Team WoS Importer:2022-09-16

Labeling of cancer cells with magnetic nanoparticles for magnetic resonance imaging - Weis, Christian; West, Adrian; Blank, Fabian; Black, Gregory; Woodward, Robert C.; Carroll, Matthew R. J.; Mainka, Astrid; Kartmann, René; Brandl, Anna; Bruns, Heiko; Hallam, Elizabeth; Shaw, Jeremy; et al. (Magnetic Resonance in Medicine, 2014)
The process of invasion and metastasis formation of tumor cells can be studied by following the migration of labeled cells over prolonged time periods. This report investigates the applicability of iron oxide nanoparticles as a magnetic resonance imaging (MRI) contrast agent for cell labeling.?Fe2 O3 nanoparticles prepared with direct flame spray pyrolysis are biofunctionalized with poly-l-lysine (PLL). The nanoparticles within the cells were observed with transmission electron microscopy, bright-field microscopy, and magnetorelaxometry. MRI of labeled cells suspended in agarose was used to estimate the detection limit.PLL-coated particles are readily taken up, stored in intracellular clusters, and gradually degraded by the cells. During cell division, the nanoparticle clusters are divided and split between daughter cells. The MRI detection limit was found to be 25 cells/mm(3) for R2*, and 70 cells/mm(3) for R2. The iron specificity, however, was higher for R2 images. Due to the degradation of intracellular ?Fe2 O3 to paramagnetic iron ions within 13 days, the R1, R2, and R2* contrast gradually decreased over this time period to approximately 50% of its initial value.These results suggest that PLL-coated ?Fe2 O3 nanoparticles can be used as an MRI contrast agent for long-term studies of cell migration. Magn Reson Med 71:1896-1905, 2014. © 2013 Wiley Periodicals, In
EVALuna2:25706

Linear and Nonlinear Rheology of Living Cells - Kollmannsberger, Philip; Fabry, Ben (Annual Review of Materials Research, 2011)

Linearity and time-scale invariance of the creep function in living cells. - Lenormand, Guillaume; Millet, Emil J.; Fabry, Ben; Butler, James P.; Fredberg, Jeffrey (Journal of the Royal Society Interface, 2004)

Localized mechanical stress induces time-dependent actin cytoskeletal remodeling and stiffening in cultured airway smooth muscle cells - Deng, L.; Fairbank, Nigel Jack; Fabry, Ben; SMITH, PAUL M.; Maksym, Geoffrey N. (American Journal of Physiology-Cell Physiology, 2004)
Mechanical stress (MS) causes cytoskeletal (CSK) and phenotypic changes in cells. Such changes in airway smooth muscle (ASM) cells might contribute to the pathophysiology of asthma. We have shown that periodic mechanical strain applied to cultured ASM cells alters the structure and expression of CSK proteins and increases cell stiffness and contractility (Smith PG, Moreno R, and Ikebe M. Am J Physiol Lung Cell Mol Physiol 272: L20-L27, 1997; and Smith PG, Deng L, Fredberg JJ, and Maksym GN. Am J Physiol Lung Cell Mol Physiol 285: L456-L463, 2003). However, the mechanically induced CSK changes, altered cell function, and their time courses are not well understood. Here we applied MS to the CSK by magnetically oscillating ferrimagnetic beads bound to the CSK. We quantified CSK remodeling by measuring actin accumulation at the sites of applied MS using fluorescence microscopy. We also measured CSK stiffness using optical magnetic twisting cytometry. We found that, during MS of up to 120 min, the percentage of beads associated with actin structures increased with time. At 60 min, 68.1 ± 1.6% of the beads were associated with actin structures compared with only 6.7 ± 2.8% before MS and 38.4 ± 5.5% in time-matched controls (P < 0.05). Similarly, CSK stiffness increased more than twofold in response to the MS compared with time-matched controls. These changes were more pronounced than observed with contractile stimulation by 80 mM KCl or 10 -4 M acetylcholine. Together, these findings imply that MS is a potent stimulus to enhance stiffness and contractility of ASM cells through CSK remodeling, which may have important implications in airway narrowing and dilation in asthm
UnivIS-Import:2015-03-09:Pub.2004.nat.dphy.IAP.lpmt.locali
Keywords: Actin cytoskeleton; Airway constriction and dilation; Airway smooth muscle cell; Asthma; Mechanical stress; Optical magnetic twisting cytometry; Stiffness

Long-term stability of aerophilic metallic surfaces underwater - Tesler, Alexander; Kolle, Stefan; Prado, Lucia; Thievessen, Ingo; Böhringer, David; Backholm, Matilda; Karunakaran, Bhuvaneshwari; Nurmi, Heikki A.; Latikka, Mika; Fischer, Lena; Stafslien, Shane; Cenev, Zoran M.; et al. (Nature Materials, 2023)
Aerophilic surfaces immersed underwater trap films of air known as plastrons. Plastrons have typically been considered impractical for underwater engineering applications due to their metastable performance. Here, we describe aerophilic titanium alloy (Ti) surfaces with extended plastron lifetimes that are conserved for months underwater. Long-term stability is achieved by the formation of highly rough hierarchically structured surfaces via electrochemical anodization combined with a low-surface-energy coating produced by a fluorinated surfactant. Aerophilic Ti surfaces drastically reduce blood adhesion and, when submerged in water, prevent adhesion of bacteria and marine organisms such as barnacles and mussels. Overall, we demonstrate a general strategy to achieve the long-term stability of plastrons on aerophilic surfaces for previously unattainable underwater applications.
CRIS-Team Scopus Importer:2023-09-29

Magnetically Guided Titania Nanotubes for Site-Selective Photocatalysis and Drug Release - Shrestha, Nabeen Kumar; Macák, Jan; Schmidt-Stein, F.; Hahn, Robert; Mierke, Claudia; Fabry, Ben; Schmuki, Patrik (Angewandte Chemie, 2008)
Quick release: The spatial and temporal delivery of active molecules (dyes or drugs) can be precisely controlled by the photocatalytic activity of TiO_2 nanotubes (see picture). The cleavage of the link between the active molecule and the nanotubes, which are filled with magnetic Fe_3O_4 nanoparticles, occurs by photoinduced chain scission under UV light; the load can be released before photodegradation by action of photogenerated radicals can occur.

Measurement of Skeletal Muscle Fiber Contractility with High-Speed Traction Microscopy - Böhringer, David; Rausch, Martin; Steinmann, Martin; Schrüfer, Stefan; Schubert, Dirk W.; Haertl, Annamaria; Mark, Christoph; Fabry, Ben (BIOPHYSICAL JOURNAL, 2020)
CRIS-Team WoS Importer:2020-03-13

Measurement of Skeletal Muscle Fiber Contractility with High-Speed Traction Microscopy - Rausch, Martin; Böhringer, David; Steinmann, Martin; Schubert, Dirk W.; Schrüfer, Stefan; Mark, Christoph; Fabry, Ben (Biophysical Journal, 2020)
We describe a technique for simultaneous quantification of the contractile forces and cytosolic calcium dynamics of muscle fibers embedded in three-dimensional biopolymer gels under auxotonic loading conditions. We derive a scaling law for linear elastic matrices such as basement membrane extract hydrogels (Matrigel) that allows us to measure contractile force from the shape of the relaxed and contracted muscle cell and the Young's modulus of the matrix without further knowledge of the matrix deformations surrounding the cell and without performing computationally intensive inverse force reconstruction algorithms. We apply our method to isolated mouse flexor digitorum brevis (FDB) fibers that are embedded in 10 mg/mL Matrigel. Upon electrical stimulation, individual FDB fibers show twitch forces of 0.37 ± 0.15 μN and tetanic forces (100-Hz stimulation frequency) of 2.38 ± 0.71 μN, corresponding to a tension of 0.44 ± 0.25 kPa and 2.53 ± 1.17 kPa, respectively. Contractile forces of FDB fibers increase in response to caffeine and the troponin-calcium stabilizer tirasemtiv, similar to responses measured in whole muscle. From simultaneous high-speed measurements of cell length changes and cytosolic calcium concentration using confocal line scanning at a frequency of 2048 Hz, we show that twitch and tetanic force responses to electric pulses follow the low-pass filtered calcium signal. In summary, we present a technically simple high-speed method for measuring contractile forces and cytosolic calcium dynamics of single muscle fibers. We expect that our method will help to reduce preparation time, costs, and the number of sacrificed animals needed for experiments such as drug testing.
CRIS-Team Scopus Importer:2020-01-24

Mechanical control of cyclic AMP signalling and gene transcription through integrins - Meyer, Christian J.; Alenghat, Francis J.; Rim, Paul; Fong, Jenny Hwai-Jen; Fabry, Ben; Ingber, Donald E. (Nature Cell Biology, 2000)

Mechanical plasticity of cells - Bonakdar, Navid; Gerum, Richard; Kuhn, Michael; Spörrer, Marina; Lippert, Anna Helena; Schneider, Werner; Aifantis, Katerina E.; Fabry, Ben (Nature Materials, 2016)

Mechanical properties of cultured human airway smooth muscle cells from 0.05 to 0.4 Hz - Maksym, Geoffrey N.; Fabry, Ben; Butler, James P.; Navajas, Daniel; Tschumperlin, Daniel J.; Laporte, Johanne D.; Fredberg, Jeffrey (Journal of Applied Physiology, 2000)

Mechanical properties of cultured human airway smooth muscle cells from 0.05 to 0.4 Hz - Maksym, Geoffrey N.; Fabry, Ben; Butler, James P.; Navajas, Daniel; Tschumperlin, Daniel J.; Laporte, Johanne D.; Fredberg, Jeffrey (Journal of Applied Physiology, 2000)

Mechano-coupling and regulation of contractility by the vinculin tail domain - Goldmann, Wolfgang; Mierke, Claudia; Kollmannsberger, Philip; Zitterbart, Daniel Paranhos; Smith, James; Fabry, Ben; Goldmann, Wolfgang Heinrich (Biophysical Journal, 2007)
UnivIS-Import:2015-03-09:Pub.2007.nat.dphy.IAP.lpmt.mechan

Mechanosensing of Cells in Laminin-Fuctionalized Biomembrane-Mimicking Substrates - Lautscham, Lena; Lin, Corey Y.; Auernheimer, Vera; Minner, Daniel; Goldmann, Wolfgang; Naumann, Christoph A.; Fabry, Ben (Biophysical Journal, 2013)

Mechanotransduction, asthma, and airway smooth muscle - Fabry, Ben; Fredberg, Jeffrey (Drug Discovery Today: Disease Models, 2007)

Mechanotransduction: use the force(s) - Paluch, Ewa K.; Nelson, Celeste; Biais, Nicolas; Fabry, Ben; Möller, Jens; Pruit, Beth L.; Wollnik, Carina; Kudryasheva, Galina; Rehfeldt, Florian; federle, walter (BMC Biology, 2015)

Mesenchymal-Like Migration Strategies of Immune Cells in a 3D Environment - Czerwinski, Tina; Mark, Christoph; Roessner, Susanne; Bosch-Voskens, Caroline; Bhattacharjee, Tapomoy; Angelini, Thomas E.; Fabry, Ben (BIOPHYSICAL JOURNAL, 2020)
CRIS-Team WoS Importer:2020-03-13

micrObs – A customizable time-lapse camera for ecological studies - Winterl, Alexander; Richter, Sebastian; Houstin, Aymeric; Nesterova, Anna P.; Bonadonna, Francesco; Schneider, Werner; Fabry, Ben; Le Bohec, Céline; Paranhos Zitterbart, Daniel (HardwareX, 2020)
Camera traps for motion-triggered or continuous time-lapse recordings are readily available on the market. For demanding applications in ecology and environmental sciences, however, commercial systems often lack flexibility to freely adjust recording time intervals, suffer from mechanical component wear, and can be difficult to combine with auxiliary sensors such as GPS, weather stations, or light sensors. We present a robust time-lapse camera system that has been operating continuously since 2013 under the harsh climatic conditions of the Antarctic and Subantarctic regions. Thus far, we have recorded over one million images with individual cameras. The system consumes 122 mW of power in standby mode and captures up to 200,000 high-resolution (16 MPix) images without maintenance such as battery or image memory replacement. It offers time-lapse intervals between 2 s and 1 h, low-light or night-time power saving, and data logging capabilities for additional inputs such as GPS and weather data.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Automated camera system; Collective behavior; Ecology; Image processing; Remote sensing; Wildlife monitoring

Microconstriction Arrays for High-Throughput Quantitative Measurements of Cell Mechanical Properties - Lange, Janina; Steinwachs, Julian; Kolb, Thorsten; Lautscham, Lena; Harder, Irina; Whyte, Graeme; Fabry, Ben (Biophysical Journal, 2015)

Microrheology of human lung epithelial cells measured by atomic force microscopy - Alcaraz, Jordi; Buscemi, Lara; Grabulosa, Mireia Herrando; Trepat, Xavier; Fabry, Ben; Farrè, Ramon; Navajas, Daniel (Biophysical Journal, 2003)

Migration in Confined 3D Environments Is Determined by a Combination of Adhesiveness, Nuclear Volume, Contractility, and Cell Stiffness - Lautscham, Lena; Kaemmerer, Christoph; Lange, Janina; Kolb, Thorsten; Mark, Christoph; Schilling, Achim; Strissel, Pamela; Strick, Reiner; Gluth, Caroline Laura Maria; Rowat, Amy C.; Metzner, Claus; Fabry, Ben (Biophysical Journal, 2015)
In cancer metastasis and other physiological processes, cells migrate through the three-dimensional (3D) extracellular matrix of connective tissue and must overcome the steric hindrance posed by pores that are smaller than the cells. It is currently assumed that low cell stiffness promotes cell migration through confined spaces, but other factors such as adhesion and traction forces may be equally important. To study 3D migration under confinement in a stiff (1.77 MPa) environment, we use soft lithography to fabricate polydimethylsiloxane (PDMS) devices consisting of linear channel segments with 20 ?m length, 3.7 ?m height, and a decreasing width from 11.2 to 1.7 ?m. To study 3D migration in a soft (550 Pa) environment, we use self-assembled collagen networks with an average pore size of 3 ?m. We then measure the ability of four different cancer cell lines to migrate through these 3D matrices, and correlate the results with cell physical properties including contractility, adhesiveness, cell stiffness, and nuclear volume. Furthermore, we alter cell adhesion by coating the channel walls with different amounts of adhesion proteins, and we increase cell stiffness by overexpression of the nuclear envelope protein lamin A. Although all cell lines are able to migrate through the smallest 1.7 ?m channels, we find significant differences in the migration velocity. Cell migration is impeded in cell lines with larger nuclei, lower adhesiveness, and to a lesser degree also in cells with lower contractility and higher stiffness. Our data show that the ability to overcome the steric hindrance of the matrix cannot be attributed to a single cell property but instead arises from a combination of adhesiveness, nuclear volume, contractility, and cell stiffness.
EVALuna2:17547

Multiple cyclic nucleotide-gated channels coordinate calcium oscillations and polar growth of root hairs - Brost, Christa; Studtrucker, Tanja; Reimann, Ronny; Denninger, Philipp; Czekalla, Jennifer; Krebs, Melanie; Fabry, Ben; Schumacher, Karin; Grossmann, Guido; Dietrich, Petra (Plant Journal, 2019)
Calcium gradients underlie polarization in eukaryotic cells. In plants, a tip-focused Ca2+-gradient is fundamental for rapid and unidirectional cell expansion during epidermal root hair development. Here we report that three members of the cyclic nucleotide-gated channel family are required to maintain cytosolic Ca2+ oscillations and the normal growth of root hairs. CNGC6, CNGC9 and CNGC14 were expressed in root hairs, with CNGC9 displaying the highest root hair specificity. In individual channel mutants, morphological defects including root hair swelling and branching, as well as bursting, were observed. The developmental phenotypes were amplified in the three cngc double mutant combinations. Finally, cngc6/9/14 triple mutants only developed bulging trichoblasts and could not form normal root hair protrusions because they burst after the transition to the rapid growth phase. Prior to developmental defects, single and double mutants showed increasingly disturbed patterns of Ca2+ oscillations. We conclude that CNGC6, CNGC9 and CNGC14 fulfill partially but not fully redundant functions in generating and maintaining tip-focused Ca2+ oscillations, which are fundamental for proper root hair growth and polarity. Furthermore, the results suggest that these calmodulin-binding and Ca2+-permeable channels organize a robust tip-focused oscillatory calcium gradient, which is not essential for root hair initiation but is required to control the integrity of the root hair after the transition to the rapid growth phase. Our findings also show that root hairs possess a large ability to compensate calcium-signaling defects, and add new players to the regulatory network, which coordinates cell wall properties and cell expansion during polar root hair growth.
CRIS-Team Scopus Importer:2019-09-03
Keywords: Arabidopsis thaliana; calcium channel; polar growth; R-GECO1; RootChip; trichoblast

N-cadherin-functionalized polymer-tethered multi-bilayer: a cell surface-mimicking substrate to probe cellular mechanosensitivity - Ge, Y.; Lin, N. H.; Lautscham, Lena; Goldmann, Wolfgang; Fabry, Ben; Naumann, Christoph A. (Soft Matter, 2016)

NEDD9 stabilizes focal adhesions, increases binding to the extra-cellular matrix and differentially effects 2D versus 3D cell migration - Zhong, Jessie; Baquiran, Jamie B.; Bonakdar, Navid; Lees, Justin; Ching, Yu Wooi; Pugacheva, Elena; Fabry, Ben; O'Neill, Geraldine Margarete (PLoS ONE, 2012)

NEDD9 stabilizes focal adhesions, increases binding to the extra-cellular matrix and differentially effects 2D versus 3D cell migration - Zhong, Jessie; Baquiran, Jamie B.; Bonakdar, Navid; Lees, Justin; Ching, Yu Wooi; Pugacheva, Elena; Fabry, Ben; O'Neill, Geraldine Margarete (PLoS ONE, 2012)

Neutrophil morphology and migration are affected by substrate elasticity - Oakes, Patrick W.; Patle, Dipan C.; Morin, Nicole A.; Paranhos Zitterbart, Daniel; Fabry, Ben; Reichner, Jonathan S.; Tang, Jay X. (Blood, 2009)

Noise and critical phenomena in biochemical signaling cycles at small molecule numbers - Fabry, Ben; Metzner, Claus; Sajitz-Hermstein, M.; Schmidberger, M. (Physical Review E - Statistical, Nonlinear, and Soft Matter Physics, 2009)

Noncanonical WNT5A controls the activation of latent TGF-β to drive fibroblast activation and tissue fibrosis - Trinh-Minh, Thuong; Chen, Chih-Wei; Tran-Manh, Cuong; Li, Yi Nan; Zhu, Honglin; Zhou, Xiang; Chakraborty, Debomita; Zhang, Yun; Rauber, Simon; Dees, Clara; Lin, Neng-Yu; Kah, Delf-Thorge Eric; et al. (Journal of Clinical Investigation, 2024)
Transforming growth factor β (TGF-β) signaling is a core pathway of fibrosis, but the molecular regulation of the activation of latent TGF-β remains incompletely understood. Here, we demonstrate a crucial role of WNT5A/JNK/ROCK signaling that rapidly coordinates the activation of latent TGF-β in fibrotic diseases. WNT5A was identified as a predominant noncanonical WNT ligand in fibrotic diseases such as systemic sclerosis, sclerodermatous chronic graft-versus-host disease, and idiopathic pulmonary fibrosis, stimulating fibroblast-to-myofibroblast transition and tissue fibrosis by activation of latent TGF-β. The activation of latent TGF-β requires rapid JNK- and ROCK-dependent cytoskeletal rearrangements and integrin αV (ITGAV). Conditional ablation of WNT5A or its downstream targets prevented activation of latent TGF-β, rebalanced TGF-β signaling, and ameliorated experimental fibrosis. We thus uncovered what we believe to be a novel mechanism for the aberrant activation of latent TGF-β in fibrotic diseases and provided evidence for targeting WNT5A/JNK/ROCK signaling in fibrotic diseases as a new therapeutic approach.
CRIS-Team Scopus Importer:2024-05-24
Keywords: Dermatology; Fibrosis; Pulmonology

Nonlinear viscoelasticity of adherent cells is controlled by cytoskeletal tension - Kollmannsberger, Philip; Mierke, Claudia; Fabry, Ben (Soft Matter, 2011)

NR4A1 Regulates Motility of Osteoclast Precursors and Serves as Target for the Modulation of Systemic Bone Turnover - Scholtysek, Carina; Ipseiz, Natacha; Böhm, Christina; Krishnacoumar, Brenda; Stenzel, Martin; Czerwinski, Tina; Palumbo-Zerr, Katrin; Rothe, Tobias; Weidner, Daniela; Klej, Alexandra; Stoll, Cornelia; Distler, Jörg; et al. (Journal of Bone and Mineral Research, 2018)
NR4A1 (Nur77 or NGFI-B), an orphan member of the nuclear receptor superfamily, has been identified as a key regulator of the differentiation and function of myeloid, lymphoid, and mesenchymal cells. The detailed role of NR4A1 in bone biology is incompletely understood. Here, we report a role for NR4A1 as novel factor controlling the migration and recruitment of osteoclast precursors during bone remodeling. Myeloid-specific but not osteoblast-specific deletion of NR4A1 resulted in osteopenia due to an increase in the number of bone-lining osteoclasts. Although NR4A1-deficient osteoclast precursors displayed a regular differentiation into mature osteoclasts, they showed a hyper-motile phenotype that was largely dependent on increased osteopontin expression, suggesting that expression of NR4A1 negatively controlled osteopontin-mediated recruitment of osteoclast precursors to the trabecular bone. Pharmacological activation of NR4A1, in turn, inhibited osteopontin expression and osteopontin-dependent migration of osteoclast precursors resulted in reduced abundance of bone-resorbing osteoclasts in vivo as well as in an ameliorated bone loss after ovariectomy in mice. This study identifies NR4A1 as a crucial player in the regulation of osteoclast biology and bone remodeling and highlights this nuclear receptor as a promising target for therapeutic intervention during the treatment of osteoporosis. © 2018 The Authors. Journal of Bone and Mineral Research Published by Wiley Periodicals Inc.
EVALuna2:34484

Occupy tissue: The movement in cancer metastasis - Bradbury, Peta; Fabry, Ben; O'Neill, Geraldine Margarete (Cell Adhesion and Migration, 2012)

On the terminology for describing the length-force relationship and its changes in airway smooth muscle - Bai, T. R.; Bates, JHT; Brusasco, Vito; Camoretti-Mercado, Blanca; Chitano, Pasquale; Deng, L.; Dowell, M.; Fabry, Ben; Ford, L.E.; Fredberg, Jeffrey; Gerthoffer, William T.; Gilbert, Susan H.; et al. (Journal of Applied Physiology, 2004)

Oscillatory magnetic tweezers based on ferromagnetic beads and simple coaxial coils - Trepat, Xavier; Grabulosa, Mireia Herrando; Buscemi, Lara; Rico, Felix; Fabry, Ben; Fredberg, Jeffrey; Farrè, Ramon (Review of Scientific Instruments, 2003)

Parameter-free binarization and skeletonization of fiber networks from confocal image stacks - Krauß, Patrick; Metzner, Claus; Lange, Janina; Lang, Nadine; Fabry, Ben (PLoS ONE, 2012)
We present a method to reconstruct a disordered network of thin biopolymers, such as collagen gels, from three-dimensional (3D) image stacks recorded with a confocal microscope. The method is based on a template matching algorithm that simultaneously performs a binarization and skeletonization of the network. The size and intensity pattern of the template is automatically adapted to the input data so that the method is scale invariant and generic. Furthermore, the template matching threshold is iteratively optimized to ensure that the final skeletonized network obeys a universal property of voxelized random line networks, namely, solid-phase voxels have most likely three solid-phase neighbors in a 3×3×3 neighborhood. This optimization criterion makes our method free of user-defined parameters and the output exceptionally robust against imaging noise. © 2012 Krauss et a

Phase transitions in huddling emperor penguins - Richter, Sebastian; Gerum, Richard; Winterl, Alexander; Houstin, A.; Seifert, Maria; Peschel, J.; Fabry, Ben; Le Bohec, Celine; Paranhos Zitterbart, Daniel (Journal of Physics D: Applied Physics, 2018)
Emperor penguins (Aptenodytes forsteri) are highly adapted to the harsh conditions of the Antarctic winter: they are able to fast for up to 134 days during breeding. To conserve energy, emperor penguins form tight groups (huddles), which is key for their reproductive success. The effect of different meteorological factors on the huddling behaviour, however, is not well understood. Using time-lapse image recordings of an emperor penguin colony, we show that huddling can be described as a phase transition from a fluid to a solid state. We use the colony density as order parameter, and an apparent temperature that is perceived by the penguins as the thermodynamic variable. We approximate the apparent temperature as a linear combination of four meteorological parameters: ambient temperature, wind speed, global radiation and relative humidity. We find a wind chill factor of -2.9 °C (ms-1)-1, a humidity chill factor of -0.5 °C/%rel. humidity, and a solar radiation heating factor of 0.3 °C (Wm-2)-1. In the absence of wind, humidity and solar radiation, the phase transition temperature (50% huddling probability) is -48.2 °C for the investigated time period (May 2014). We propose that higher phase transition temperatures indicate a shrinking thermal insulation and thus can serve as a proxy for lower energy reserves of the colony, integrating pre-breeding foraging success at sea and energy expenditure at land due to environmental conditions. As current global change is predicted to have strong detrimental effects on emperor penguins within the next decades, our approach may thus contribute towards an urgently needed long-term monitoring system for assessing colony health.
CRIS-Team Scopus Importer:2022-08-05
Keywords: climate variability; collective behaviour; emperor penguin; environmental conditions; huddling; phase transition

pH-responsive anodic titanium dioxide nanotubes and nanocylinders for cancer drug delivery - Hasanzadeh Kafshgari, Morteza; Mazare, Anca Valentina; Distaso, Monica; Goldmann, Wolfgang; Peukert, Wolfgang; Fabry, Ben; Schmuki, Patrik (AMER SOC CELL BIOLOGY, 2018)

Plasticity of 3D Hydrogels Predicts Cell Biological Behavior - Malandrino, Andrea; Zhang, Huijun; Schwarm, Nico; Böhringer, David; Kah, Delf-Thorge Eric; Kuster, Christian; Boccaccini, Aldo R.; Fabry, Ben (Biomacromolecules, 2024)
Under 3D culture conditions, cells tend to spread, migrate, and proliferate better in more viscoelastic and plastic hydrogels. Here, we present evidence that the improved cell behavior is facilitated by the lower steric hindrance of a more viscoelastic and plastic matrix with weaker intermolecular bonds. To determine intermolecular bond stability, we slowly insert semispherical tipped needles (100-700 μm diameter) into alginate dialdehyde-gelatin hydrogels and measure stiffness, yield strength, plasticity, and the force at which the surface ruptures (puncture force). To tune these material properties without affecting matrix stiffness, we precross-link the hydrogels with CaCl2 droplets prior to mixing in NIH/3T3 fibroblasts and final cross-linking with CaCl2. Precross-linking introduces microscopic weak spots in the hydrogel, increases plasticity, and decreases puncture force and yield strength. Fibroblasts spread and migrate better in precross-linked hydrogels, demonstrating that intermolecular bond stability is a critical determinant of cell behavior under 3D culture conditions.
CRIS-Team Scopus Importer:2025-02-04

Plectin ensures intestinal epithelial integrity and protects colon against colitis - Krausova, Alzbeta; Buresova, Petra; Sarnova, Lenka; Oyman-Eyrilmez, Gizem; Skarda, Jozef; Wohl, Pavel; Bajer, Lukas; Sticova, Eva; Bartonova, Lenka; Pacha, Jiri; Koubkova, Gizela; Prochazka, Jan; et al. (Mucosal Immunology, 2021)
Plectin, a highly versatile cytolinker protein, provides tissues with mechanical stability through the integration of intermediate filaments (IFs) with cell junctions. Here, we hypothesize that plectin-controlled cytoarchitecture is a critical determinant of the intestinal barrier function and homeostasis. Mice lacking plectin in an intestinal epithelial cell (IEC; PleΔIEC) spontaneously developed colitis characterized by extensive detachment of IECs from the basement membrane (BM), increased intestinal permeability, and inflammatory lesions. Moreover, plectin expression was reduced in the colons of ulcerative colitis (UC) patients and negatively correlated with the severity of colitis. Mechanistically, plectin deficiency in IECs led to aberrant keratin filament (KF) network organization and the formation of dysfunctional hemidesmosomes (HDs) and intercellular junctions. In addition, the hemidesmosomal α6β4 integrin (Itg) receptor showed attenuated association with KFs, and protein profiling revealed prominent downregulation of junctional constituents. Consistent with the effects of plectin loss in the intestinal epithelium, plectin-deficient IECs exhibited remarkably reduced mechanical stability and limited adhesion capacity in vitro. Feeding mice with a low-residue liquid diet that reduced mechanical stress and antibiotic treatment successfully mitigated epithelial damage in the PleΔIEC colon.
CRIS-Team Scopus Importer:2021-03-19

Plectin-mediated cytoskeletal crosstalk controls cell tension and cohesion in epithelial sheets - Prechova, Magdalena; Adamova, Zuzana; Schweizer, Anna Lena; Maninova, Miloslava; Bauer, Andreas; Kah, Delf-Thorge Eric; Meier-Menches, Samuel M.; Wiche, Gerhard; Fabry, Ben; Gregor, Martin (The Journal of Cell Biology, 2022)
The coordinated interplay of cytoskeletal networks critically determines tissue biomechanics and structural integrity. Here, we show that plectin, a major intermediate filament-based cytolinker protein, orchestrates cortical cytoskeletal networks in epithelial sheets to support intercellular junctions. By combining CRISPR/Cas9-based gene editing and pharmacological inhibition, we demonstrate that in an F-actin-dependent context, plectin is essential for the formation of the circumferential keratin rim, organization of radial keratin spokes, and desmosomal patterning. In the absence of plectin-mediated cytoskeletal cross-linking, the aberrant keratin-desmosome (DSM)-network feeds back to the actin cytoskeleton, which results in elevated actomyosin contractility. Also, by complementing a predictive mechanical model with Förster resonance energy transfer-based tension sensors, we provide evidence that in the absence of cytoskeletal cross-linking, major intercellular junctions (adherens junctions and DSMs) are under intrinsically generated tensile stress. Defective cytoarchitecture and tensional disequilibrium result in reduced intercellular cohesion, associated with general destabilization of plectin-deficient sheets upon mechanical stress.
CRIS-Team Scopus Importer:2022-03-04

Poresizes in random line networks - Metzner, Claus; Krauß, Patrick; Fabry, Ben (arXiv, 2011)

Predicting Cell Stress and Strain during Extrusion Bioprinting - Müller, Sebastian J.; Fabry, Ben; Gekle, Stephan (Physical Review Applied, 2023)
Bioprinting of living cells can cause major shape deformations, which may severely affect cell survival and functionality. While the shear stresses occurring during cell flow through the printer nozzle have been quantified to some extent, the extensional stresses occurring as cells leave the nozzle into the free printing strand have been mostly ignored. Here we use lattice Boltzmann simulations together with a finite-element based cell model to study cell deformation inside the nozzle and at its exit. Our simulation results are in good qualitative agreement with experimental microscopy images. We show that, for cells flowing in the center of the nozzle, extensional stresses can be significant while, for cells flowing off-center, their deformation is dominated by the shear flow inside the nozzle. From the results of these simulations, we develop two simple methods that only require the printing parameters (nozzle diameter, flow rate, bioink rheology) to (i) accurately predict the maximum cell stress occurring during the three-dimensional bioprinting process and (ii) approximately predict the cell strains caused by the elongational flow at the nozzle exit.
CRIS-Team Scopus Importer:2023-07-21

Predicting plastron thermodynamic stability for underwater superhydrophobicity - Tesler, Alexander; Nurmi, Heikki A.; Kolle, Stefan; Prado, Lucia; Karunakaran, Bhuvaneshwari; Mazare, Anca Valentina; Erceg, Ina; de brito soares, Íris; Sarau, George; Christiansen, Silke; Stafslien, Shane; Alvarenga, Jack; et al. (Communications Materials, 2024)
Non-wettable surfaces, especially those capable of passively trapping air in rough protrusions, can provide surface resilience to the detrimental effects of wetting-related phenomena. However, the development of such superhydrophobic surfaces with a long-lasting entrapped air layer, called plastron, is hampered by the lack of evaluation criteria and methods that can unambiguously distinguish between stable and metastable Cassie-Baxter wetting regimes. The information to evaluate the stability of the wetting regime is missing from the commonly used contact angle goniometry. Therefore, it is necessary to determine which surface features can be used as a signature to identify thermodynamically stable plastron. Here, we describe a methodology for evaluating the thermodynamic underwater stability of the Cassie-Baxter wetting regime of superhydrophobic surfaces by measuring the surface roughness, solid-liquid area fraction, and Young’s contact angle. The method allowed the prediction of passive plastron stability for over one year of continuous submersion, the impeding of mussel and barnacle adhesion, and inhibition of metal corrosion in seawater. Such submersion-stable superhydrophobicity, in which water is repelled by a stable passive air layer trapped between the solid substrate and the surrounding liquid for extended periods at ambient conditions, opens new avenues for science and technologies that require continuous contact of solids with aqueous media. (Figure presented.).
CRIS-Team Scopus Importer:2024-07-12

Pressure-driven collective growth mechanism of planar cell colonies. - Metzner, Claus; Lange, Janina; Krauß, Patrick; Wunderling, Nico; Übelacker, Julian; Martin, Florian; Fabry, Ben (Journal of Physics D-Applied Physics, 2018)

Pressure-driven collective growth mechanism of planar cell colonies. - Metzner, Claus; Lange, Janina; Krauß, Patrick; Wunderling, Nico; Übelacker, Julian; Martin, Florian; Fabry, Ben (Journal of Physics D: Applied Physics, 2018)
The growth of cell colonies is determined by the migration and proliferation of the individual cells. This is often modeled with the Fisher-Kolmogorov (FK) equation, which assumes that cells diffuse independently from each other, but stop to proliferate when their density reaches a critial limit. However, when using measured, cell-line specific parameters, we find that the FK equation drastically underestimates the experimentally observed increase of colony radius with time. Moreover, cells in real colonies migrate radially outward with superdiffusive trajectories, in contrast to the assumption of random diffusion. We demonstrate that both dicrepancies can be resolved by assuming that cells in dense colonies are driven apart by repulsive, pressure-like forces. Using this model of proliferating repelling particles (PRP), we find that colony growth exhibits different dynamical regimes, depending on the ratio between a pressure-related equilibrium cell density and the critial density of proliferation arrest.
EVALuna2:210450

Pulling it together in three dimensions - Trepat, Xavier; Fabry, Ben; Fredberg, Jeffrey (Nature Methods, 2010)

pyTFM: A tool for traction force and monolayer stress microscopy - Bauer, Andreas; Prechová, Magdalena; Fischer, Lena; Thievessen, Ingo; Gregor, Martin; Fabry, Ben (PLoS Computational Biology, 2021)
Cellular force generation and force transmission are of fundamental importance for numerous biological processes and can be studied with the methods of Traction Force Microscopy (TFM) and Monolayer Stress Microscopy. Traction Force Microscopy and Monolayer Stress Microscopy solve the inverse problem of reconstructing cell-matrix tractions and inter- and intra-cellular stresses from the measured cell force-induced deformations of an adhesive substrate with known elasticity. Although several laboratories have developed software for Traction Force Microscopy and Monolayer Stress Microscopy computations, there is currently no software package available that allows non-expert users to perform a full evaluation of such experiments. Here we present pyTFM, a tool to perform Traction Force Microscopy and Monolayer Stress Microscopy on cell patches and cell layers grown in a 2-dimensional environment. pyTFM was optimized for ease-of-use; it is open-source and well documented (hosted at https://pytfm.readthedocs.io/) including usage examples and explanations of the theoretical background. pyTFM can be used as a standalone Python package or as an add-on to the image annotation tool ClickPoints. In combination with the ClickPoints environment, pyTFM allows the user to set all necessary analysis parameters, select regions of interest, examine the input data and intermediary results, and calculate a wide range of parameters describing forces, stresses, and their distribution. In this work, we also thoroughly analyze the accuracy and performance of the Traction Force Microscopy and Monolayer Stress Microscopy algorithms of pyTFM using synthetic and experimental data from epithelial cell patches.
CRIS-Team Scopus Importer:2021-07-09

Quantifying cell-to-cell variation in power-law rheology - Cai, PinGen; Mizutani, Yusuke; Tsuchiya, Masahiro; Maloney, John M.; Fabry, Ben; Van Vliet, Krystyn; Okajima, Takaharu (Journal of Biochemistry, Molecular Biology and Biophysics, 2013)

Rat airway smooth muscle cell during actin modulation: rheology and glassy dynamics - Laudadio, Rachel E.; Millet, Emil J.; Fabry, Ben; An, Steven S.; Butler, James P.; Fredberg, Jeffrey (American Journal of Physiology-Cell Physiology, 2005)

Remodeling of the airway smooth muscle cell: are we built of glass? - Fabry, Ben; et al. (Respiratory Physiology & Neurobiology, 2003)

Remote sensing of emperor penguin abundance and breeding success - Winterl, Alexander; Richter, Sebastian; Houstin, Aymeric; Barracho, Téo; Boureau, Matthieu; Cornec, Clément; Couet, Douglas; Cristofari, Robin; Eiselt, Claire; Fabry, Ben; Krellenstein, Adélie; Mark, Christoph; et al. (Nature Communications, 2024)
Emperor penguins (Aptenodytes forsteri) are under increasing environmental pressure. Monitoring colony size and population trends of this Antarctic seabird relies primarily on satellite imagery recorded near the end of the breeding season, when light conditions levels are sufficient to capture images, but colony occupancy is highly variable. To correct population estimates for this variability, we develop a phenological model that can predict the number of breeding pairs and fledging chicks, as well as key phenological events such as arrival, hatching and foraging times, from as few as six data points from a single season. The ability to extrapolate occupancy from sparse data makes the model particularly useful for monitoring remotely sensed animal colonies where ground-based population estimates are rare or unavailable.
CRIS-Team Scopus Importer:2024-06-14

Respiratory comfort of automatic tube compensation and inspiratory pressure support in conscious humans - Fabry, Ben; et al. (Intensive Care Medicine, 1997)

Rheology of airway smooth muscle cells is associated with cytoskeletal contractile stress - Stamenovic, Dimitrije; Suki, Bela; Fabry, Ben; Wang, Ning; Fredberg, Jeffrey (Journal of Applied Physiology, 2004)
Recently reported data from mechanical measurements of cultured airway smooth muscle cells show that stiffness of the cytoskeletal matrix is determined by the extent of static contractile stress borne by the cytoskeleton (Wang N, Tolić-Nørrelykke IM, Chen J, Mijailovich SM, Butler JP, Fredberg JJ, and Stamenović D. Am J Physiol Cell Physiol 282, C606-C616, 2002). On the other hand, rheological measurements on these cells show that cytoskeletal stiffness changes with frequency of imposed mechanical loading according to a power law (Fabry B, Maksym GN, Butler JP, Glogauer M, Navajas DF, and Fredberg JJ. Phys Rev Lett 87: 148102, 2001). In this study, we examine the possibility that these two empirical observations might be interrelated. We combine previously reported data for contractile stress of human airway smooth muscle cells with new data describing rheological properties of these cells and derive quantitative, mathematically tractable, and experimentally verifiable empirical relationships between contractile stress and indexes of cell rheology. These findings reveal an intriguing role of the contractile stress: although it maintains structural stability of the cell under applied mechanical loads, it may also regulate rheological properties of the cytoskeleton, which are essential for other cell function
UnivIS-Import:2015-03-09:Pub.2004.nat.dphy.IAP.lpmt.rheolo
Keywords: Contractility; Cytometry; Mechanics; Power law; Stiffness

Robust Pore Size Analysis of Filamentous Networks from Three-Dimensional Confocal Microscopy - Mickel, Walter; Münster, Stefan; Jawerth, Louise M.; Vader, David A.; Weitz, David A.; Sheppard, Adrian P.; Mecke, Klaus; Fabry, Ben; Schröder-Turk, Gerd (Biophysical Journal, 2008)
We describe a robust method for determining morphological properties of. lamentous biopolymer networks, such as collagen or other connective tissue matrices, from confocal microscopy image stacks. Morphological properties including pore size distributions and percolation thresholds are important for transport processes, e. g., particle diffusion or cell migration through the extracellular matrix. The method is applied to fluorescently labeled fiber networks prepared from rat-tail tendon and calf-skin collagen, at concentrations of 1.2, 1.6, and 2.4 mg/ml. The collagen fibers form an entangled and branched network. The medial axes, or skeletons, representing the collagen fibers are extracted from the image stack by threshold intensity segmentation and distance-ordered homotopic thinning. The size of the fiuid pores as defined by the radii of largest spheres that fit into the cavities between the collagen fibers is derived from Euclidean distance maps and maximal covering radius transforms of the fluid phase. The size of the largest sphere that can traverse the fluid phase between the collagen fibers across the entire probe, called the percolation threshold, was computed for both horizontal and vertical directions. We demonstrate that by representing the fibers as the medial axis the derived morphological network properties are both robust against changes of the value of the segmentation threshold intensity and robust to problems associated with the point-spread function of the imaging system. We also provide empirical support for a recent claim that the percolation threshold of a fiber network is close to the fiber diameter for which the Euler index of the networks becomes zero.

Role of ERK MAP kinases in responses of cultured human airway smooth muscle cells to IL-1beta - Laporte, Johanne D.; Moore, Paul E.; Abraham, Jonathan H.; Maksym, Geoffrey N.; Fabry, Ben; Panettieri, Reynold A.; Shore, Stephanie A. (American Journal of Physiology, 1999)

Role of Heat Shock Protein 27 in Cytoskeletal Remodeling of the Airway Smooth Muscle Cell - An, Steven S.; Fabry, Ben; Mellema, Mathew; Bursac, Predrag; Gerthoffer, William T.; Kayyali, Usamah S.; Gaestel, Matthias; Shore, Stephanie A.; Fredberg, Jeffrey (Journal of Applied Physiology, 2004)

Scaling the microrheology of living cells - Fabry, Ben; Maksym, Geoffrey N.; Butler, James P.; Glogauer, Michael; Navajas, Daniel; Fredberg, Jeffrey (FOUND PHYS LETT, 2001)

Silicone-Based Lubricant-Infused Slippery Coating Covalently Bound to Aluminum Substrates for Underwater Applications - Prado, Lucia; Böhringer, David; Mazare, Anca Valentina; Sotelo, Lamborghini; Sarau, George; Christiansen, Silke; Fabry, Ben; Schmuki, Patrik; Virtanen, Sannakaisa; Goldmann, Wolfgang; Tesler, Alexander (ACS Applied Materials and Interfaces, 2023)
Wetting of solid surfaces is crucial for biological and industrial processes but is also associated with several harmful phenomena such as biofouling and corrosion that limit the effectiveness of various technologies in aquatic environments. Despite extensive research, these challenges remain critical today. Recently, we have developed a facile UV-grafting technique to covalently attach silicone-based coatings to solid substrates. In this study, the grafting process was evaluated as a function of UV exposure time on aluminum substrates. While short-time exposure to UV light results in the formation of lubricant-infused slippery surfaces (LISS), a flat, nonporous variant of slippery liquid-infused porous surfaces, longer exposure leads to the formation of semi-rigid cross-linked polydimethylsiloxane (PDMS) coatings, both covalently bound to the substrate. These coatings were exposed to aquatic media to evaluate their resistance to corrosion and biofouling. While the UV-grafted cross-linked PDMS coating effectively inhibits aluminum corrosion in aquatic environments and allows organisms to grow on the surface, the LISS coating demonstrates improved corrosion resistance but inhibits biofilm adhesion. The synergy between facile and low-cost fabrication, rapid binding kinetics, eco-friendliness, and nontoxicity of the applied materials to aquatic life combined with excellent wetting-repellent characteristics make this technology applicable for implementation in aquatic environments.
CRIS-Team Scopus Importer:2023-07-21
Keywords: anti-biofouling; biofilms; corrosion resistance; cross-linking; lubricant-infused slippery surfaces; polydimethylsiloxane; UV-grafting

Simple model of cytoskeletal fluctuations - Metzner, Claus; Raupach, Carina; Paranhos Zitterbart, Daniel; Fabry, Ben (Physical Review E, 2007)
The spontaneous motion of microbeads bound to the cytoskeleton of living cells is not an ordinary random walk. Unlike Brownian motion, the mean-square displacement undergoes a transition from subdiffusive to superdiffusive behavior with time. This transition is associated with characteristic changes of the turning angle distribution. Recent experimental data demonstrated that force fluctuations measured in an elastic hydrogel matrix beneath the cell correlate with the bead motion. These data indicate that the bead trajectory is driven by motor forces originating from the actomyosin network and that cytoskeletal remodeling processes with short- and long-time dynamics are mainly responsible for the non-Brownian behavior. We show that the essential statistical properties of the spontaneous bead motion can be reproduced by a particle diffusing in a potential well with a slowly drifting minimum position. Based on this simple model, which can be solved analytically, we develop a biologically plausible numerical model of a tensed and continuously remodeling actomyosin network that accounts quantitatively for the measured data. © 2007 The American Physical Society.
UnivIS-Import:2015-03-09:Pub.2007.nat.dphy.IAP.lpmt.simple

Single-cell response to stiffness exhibits muscle-like behavior - Mitrossilis, Démosthène; Fouchard, Jonathan; Guiroy, Axel; Desprat, Nicolas; Nicolas Rodriguez, Nicolas; Fabry, Ben; Asnacios, Atef (Proceedings of the National Academy of Sciences of the United States of America, 2009)

Size-selective separation of macromolecules by nanochannel titania membrane with self-cleaning (declogging) ability - Roy, Poulumi; Dey, Tuli; Lee, Kiyoung; Kim, Doo Hun; Fabry, Ben; Schmuki, Patrik (Journal of the American Chemical Society, 2010)

Strain history dependence of the nonlinear stress response of fibrin and collagen networks - Münster, Stefan; Jawerth, Louise M.; Leslie, Beverly A.; Weitz, Jeffrey I.; Fabry, Ben; Weitz, David (Proceedings of the National Academy of Sciences of the United States of America, 2013)

Stress controls the mechanics of collagen networks - Licup, Albert James; Münster, Stefan; Sharma, Abhinav; Sheinman, Michael; Jawerth, Louise M.; Fabry, Ben; Weitz, David A.; MacKintosh, Fred C. (Proceedings of the National Academy of Sciences of the United States of America, 2015)

Stress fluctuations and motion of cytoskeletal-bound markers - Raupach, Carina; Paranhos Zitterbart, Daniel; Mierke, Claudia; Metzner, Claus; Müller, Frank A.; Fabry, Ben (Physical Review E, 2007)
Cytoskeletal (CSK) dynamics such as remodeling and reorganization can be studied by tracking the spontaneous motion of CSK-bound particles. Particle motion is thought to be driven by local, ATP-dependent intracellular force fluctuations due to polymerization processes and motor proteins, and to be impeded by a viscoelastic, metastable cytoskeletal network. The mechanisms that link particle motion to force fluctuations and the CSK dynamics remain unclear. We report simultaneous measurements of the spontaneous motion of CSK-bound particles and of cellular force fluctuations. Cellular force fluctuations were measured by tracking fluorescent markers embedded in an elastic polyacrylamide hydrogel substrate that served as an extracellular matrix (ECM). The motion of CSK-bound particles and markers embedded in the ECM showed both persistence and superdiffusive behavior. Moreover, the movements of CSK-bound beads were temporally and spatially correlated with force fluctuations in the ECM. The findings suggest that the spontaneous motion of CSK-bound beads is driven not by random, local stress fluctuations within a viscoelastic continuum or cage, but rather by stress fluctuations within a tensed and constantly remodeling CSK network that transmits stresses over considerable distances to the ECM. © 2007 The American Physical Society.
UnivIS-Import:2015-03-09:Pub.2007.nat.dphy.IAP.lpmt.stress

Stress relaxation amplitude of hydrogels determines migration, proliferation, and morphology of cells in 3-D culture - Hazur, Jonas; Endrizzi, Nadine; Schubert, Dirk W.; Boccaccini, Aldo R.; Fabry, Ben (Biomaterials Science, 2021)
The viscoelastic behavior of hydrogel matrices sensitively influences the cell behavior in 3-D culture and biofabricated tissue model systems. Previous reports have demonstrated that cells tend to adhere, spread, migrate and proliferate better in hydrogels with pronounced stress relaxation. However, it is currently unknown if cells respond more sensitively to the amplitude of stress relaxation, or to the relaxation time constant. To test this, we compare the behavior of fibroblasts cultured for up to 10 days in alginate and oxidized alginate hydrogels with similar Young's moduli but diverging stress relaxation behavior. We find that fibroblasts elongate, migrate and proliferate better in hydrogels that display a higher stress relaxation amplitude. By contrast, the cells' response to the relaxation time constant was less pronounced and less consistent. Together, these data suggest that it is foremost the stress relaxation amplitude of the matrix that determines the ability of cells to locally penetrate and structurally remodel the matrix on a molecular level, which subsequently leads to better spreading, faster migration, and higher cell proliferation. We conclude that the stress relaxation amplitude is a central design parameter for optimizing cell behavior in 3-D hydrogels.
CRIS-Team WoS Importer:2021-12-10

Structural organisation and dynamics in king penguin colonies - Gerum, Richard; Richter, Sebastian; Fabry, Ben; Le Bohec, Céline; Bonadonna, Francesco; Nesterova, Anna; Paranhos Zitterbart, Daniel (Journal of Physics D-Applied Physics, 2018)

Structure and mechanics of fibrin clots formed under mechanical perturbation - Münster, Stefan; Jawerth, Louise M.; Fabry, Ben; Weitz, David A. (Journal of Thrombosis and Haemostasis, 2013)

Superstatistical analysis and modelling of heterogeneous random walks - Metzner, Claus; Mark, Christoph; Steinwachs, Julian; Lautscham, Lena; Stadler, Franz; Fabry, Ben (Nature Communications, 2015)

Superstatistical analysis and modelling of heterogeneous random walks - Metzner, Claus; Mark, Christoph; Steinwachs, Julian; Lautscham, Lena; Stadler, Franz; Fabry, Ben (Nature Communications, 2015)

Support of spontaneous breathing in the intubated patient: automatic tube compensation (ATC) and proportional assist ventilation (PAV) - Fabry, Ben; et al. (Acta Anaesthesiologica Scandinavica, 1997)

The cytoskeleton as a soft glassy material. In: Cytoskeletal Mechanics: Models and Measurements. - Fredberg, Jeffrey; Fabry, Ben (Cambridge University Press, 2006)

The desmin mutation R349P increases contractility and fragility of stem cell-generated muscle micro-tissues - Spörrer, Marina; Kah, Delf-Thorge Eric; Gerum, Richard; Reischl, Barbara; Huraskin, Danyil; Dessalles, Claire A.; Schneider, Werner; Goldmann, Wolfgang; Herrmann, Harald; Thievessen, Ingo; Clemen, Christoph S.; Friedrich, Oliver; et al. (Neuropathology and Applied Neurobiology, 2021)
Aims: Desminopathies comprise hereditary myopathies and cardiomyopathies caused by mutations in the intermediate filament protein desmin that lead to severe and often lethal degeneration of striated muscle tissue. Animal and single cell studies hinted that this degeneration process is associated with massive ultrastructural defects correlating with increased susceptibility of the muscle to acute mechanical stress. The underlying mechanism of mechanical susceptibility, and how muscle degeneration develops over time, however, has remained elusive. Methods: Here, we investigated the effect of a desmin mutation on the formation, differentiation, and contractile function of in vitro-engineered three-dimensional micro-tissues grown from muscle stem cells (satellite cells) isolated from heterozygous R349P desmin knock-in mice. Results: Micro-tissues grown from desmin-mutated cells exhibited spontaneous unsynchronised contractions, higher contractile forces in response to electrical stimulation, and faster force recovery compared with tissues grown from wild-type cells. Within 1 week of culture, the majority of R349P desmin-mutated tissues disintegrated, whereas wild-type tissues remained intact over at least three weeks. Moreover, under tetanic stimulation lasting less than 5 s, desmin-mutated tissues partially or completely ruptured, whereas wild-type tissues did not display signs of damage. Conclusions: Our results demonstrate that the progressive degeneration of desmin-mutated micro-tissues is closely linked to extracellular matrix fibre breakage associated with increased contractile forces and unevenly distributed tensile stress. This suggests that the age-related degeneration of skeletal and cardiac muscle in patients suffering from desminopathies may be similarly exacerbated by mechanical damage from high-intensity muscle contractions. We conclude that micro-tissues may provide a valuable tool for studying the organization of myocytes and the pathogenic mechanisms of myopathies.
CRIS-Team Scopus Importer:2021-12-17
Keywords: desmin; desminopathy; micro-tissue; skeletal muscle physiology; tissue engineering

The focal adhesion protein β-parvin controls cardiomyocyte shape and sarcomere assembly in response to mechanical load - Thievessen, Ingo; Suhr, Frank; Vergarajauregui, Silvia; Böttcher, Ralph T.; Brixius, Klara; Rosenberger, Georg; Fleischmann, Bernd K.; Ghanem, Alexander; Krüger, Marcus; Engel, Felix; Fabry, Ben; Bloch, Wilhelm; et al. (Current Biology, 2022)
Physiological and pathological cardiac stress induced by exercise and hypertension, respectively, increase the hemodynamic load for the heart and trigger specific hypertrophic signals in cardiomyocytes leading to adaptive or maladaptive cardiac hypertrophy responses involving a mechanosensitive remodeling of the contractile cytoskeleton. Integrins sense load and have been implicated in cardiac hypertrophy, but how they discriminate between the two types of cardiac stress and translate mechanical loads into specific cytoskeletal signaling pathways is not clear. Here, we report that the focal adhesion protein β-parvin is highly expressed in cardiomyocytes and facilitates the formation of cell protrusions, the serial assembly of newly synthesized sarcomeres, and the hypertrophic growth of neonatal rat ventricular cardiomyocytes (NRVCs) in vitro. In addition, physiological mechanical loading of NRVCs by either the application of cyclic, uni-axial stretch, or culture on physiologically stiff substrates promotes NRVC elongation in a β-parvin-dependent manner, which is achieved by binding of β-parvin to α/β-PIX, which in turn activates Rac1. Importantly, loss-of-function studies in mice also revealed that β-parvin is essential for the exercise-induced cardiac hypertrophy response in vivo. Our results identify β-parvin as a novel mechano-responsive signaling hub in hypertrophic cardiomyocytes that drives cell elongation in response to physiological mechanical loads.
CRIS-Team Scopus Importer:2022-08-05
Keywords: affixin; cardiac hypertrophy; integrin-linked kinase; mechanotransduction; Rac1; sarcomere assembly; β-parvin

The focal adhesion targeting domain of p130Cas confers a mechanosensing function - Bradbury, Peta; Turner, Kylie; Mitchell, Camilla; Griffin, Kaitlyn Rose; Middlemiss, Shiloh; Lau, Loretta; Dagg, Rebecca; Taran, Elena; Cooper-White, Justin; Fabry, Ben; O'Neill, Geraldine Margarete (Journal of Cell Science, 2017)

The IsoStretcher: An isotropic cell stretch device to study mechanical biosensor pathways in living cells. - Schürmann, Sebastian; Wagner, Sören; Herlitze, Simon; Fischer, C.; Gumbrecht, S.; Wirth-Hücking, Anette; Prölß, Gerhard; Lautscham, Lena; Fabry, Ben; Goldmann, Wolfgang; Nikolova-Krstevski, V.; Martinac, B.; et al. (Biosensors and Bioelectronics, 2016)
Mechanosensation in many organs (e.g. lungs, heart, gut) is mediated by biosensors (like mechanosensitive ion channels), which convert mechanical stimuli into electrical and/or biochemical signals. To study those pathways, technical devices are needed that apply strain profiles to cells, and ideally allow simultaneous live-cell microscopy analysis. Strain profiles in organs can be complex and multiaxial, e.g. in hollow organs. Most devices in mechanobiology apply longitudinal uniaxial stretch to adhered cells using elastomeric membranes to study mechanical biosensors. Recent approaches in biomedical engineering have employed intelligent systems to apply biaxial or multiaxial stretch to cells. Here, we present an isotropic cell stretch system (IsoStretcher) that overcomes some previous limitations. Our system uses a rotational swivel mechanism that translates into a radial displacement of hooks attached to small circular silicone membranes. Isotropicity and focus stability are demonstrated with fluorescent beads, and transmission efficiency of elastomer membrane stretch to cellular area change in HeLa/HEK cells. Applying our system to lamin-A overexpressing fibrosarcoma cells, we found a markedly reduced stretch of cell area, indicative of a stiffer cytoskeleton. We also investigated stretch-activated Ca(2+) entry into atrial HL-1 myocytes. 10% isotropic stretch induced robust oscillating increases in intracellular Fluo-4 Ca(2+) fluorescence. Store-operated Ca(2+) entry was not detected in these cells. The Isostretcher provides a useful versatile tool for mechanobiolog

The origin of traveling waves in an emperor penguin huddle - Gerum, Richard; Fabry, Ben; Metzner, Claus; Beaulieu, Michaël; Ancel, André; Paranhos Zitterbart, Daniel (New Journal of Physics, 2013)

The role of focal adhesion anchoring domains of CAS in mechanotransduction - Braniš, Jaroslav; Pataki, Csilla; Spörrer, Marina; Gerum, Richard; Mainka, Astrid; Cermak, Vladimir; Goldmann, Wolfgang; Fabry, Ben; Brabek, Jan; Rosel, Daniel (Scientific Reports, 2017)

The role of focal adhesion anchoring domains of CAS in mechanotransduction - Braniš, Jaroslav; Pataki, Csilla; Spörrer, Marina; Gerum, Richard; Mainka, Astrid; Cermak, Vladimir; Goldmann, Wolfgang; Fabry, Ben; Brabek, Jan; Rosel, Daniel (Scientific Reports, 2017)

The role of focal adhesion anchoring domains of CAS in mechhttps://cris.fau.de/converis/mypages/edit/Publication/1080200/default#anotransduction - Braniš, Jaroslav; Pataki, Csilla; Spörrer, Marina; Gerum, Richard; Mainka, Astrid; Cermak, Vladimir; Goldmann, Wolfgang; Fabry, Ben; Brabek, Jan; Rosel, Daniel (Scientific Reports, 2017)

The role of the tissue microenvironment in the regulation of cancer cell motility and invasion - Brabek, Jan; Mierke, Claudia; Roesel, Daniel; Vesely, Pavel; Fabry, Ben (Cell Communication and Signaling, 2010)

Three-dimensional force microscopy of cells in biopolymer networks - Steinwachs, Julian; Metzner, Claus; Skodzek, Kai; Lang, Nadine; Thievessen, Ingo; Mark, Christoph; Münster, Stefan; Aifantis, Katerina E.; Fabry, Ben (Nature Methods, 2016)

Time constant/volume relationship of passive expiration in mechanically ventilated ARDS patients - Guttmann, Josef; Eberhard, Luc; Fabry, Ben; Bertschmann, W.; Zeravik, J.; Adolph, Michael, Joachim Eckart; Wolff, G. (European Respiratory Journal, 1995)

Time course and heterogeneity of contractile responses in cultured human airway smooth muscle cells - Fabry, Ben; Maksym, Geoffrey N.; Shore, Stephanie A.; Moore, Paul E.; Panettieri, Reynold A.; Butler, James P.; Fredberg, Jeffrey (Journal of Applied Physiology, 2001)

Time scale and other invariants of integrative mechanical behavior in living cells - Fabry, Ben; Maksym, Geoffrey N.; Butler, James P.; Glogauer, Michael; Navajas, Daniel; Taback, Nathan A.; Millet, Emil J.; Fredberg, Jeffrey (Physical Review E - Statistical, Nonlinear, and Soft Matter Physics, 2003)

Traction fields, moments, and strain energy that cells exert on their surroundings - Butler, James P.; Tolić-Nørrelykke, Iva Marija; Fabry, Ben; Fredberg, Jeffrey (American Journal of Physiology-Cell Physiology, 2002)

Traction Force Microscopy in 3-Dimensional Extracellular Matrix Networks. - Cóndor, Mar; Steinwachs, Julian; Mark, Christoph; Garcia-Aznar, Jose M.; Fabry, Ben (Current protocols in cell biology, 2017)
Cell migration through a three-dimensional (3-D) matrix depends strongly on the ability of cells to generate traction forces. To overcome the steric hindrance of the matrix, cells need to generate sufficiently high traction forces but also need to distribute these forces spatially in a migration-promoting way. This unit describes a protocol to measure spatial maps of cell traction forces in 3-D biopolymer networks such as collagen, fibrin, or Matrigel. Traction forces are computed from the relationship between measured force-induced matrix deformations surrounding the cell and the known mechanical properties of the matrix. The method does not rely on knowledge of the cell surface coordinates and takes nonlinear mechanical properties of the matrix into account. © 2017 by John Wiley & Sons, Inc.

Treatment of keratinocytes with 4-phenylbutyrate in epidermolysis bullosa: Lessons for therapies in keratin disorders - Spörrer, Marina; Prochnicki, Ania; Tölle, Regine C.; Nyström, Alexander; Esser, Philipp R.; Homberg, Melanie; Athanasiou, Ioannis; Zingkou, Eleni; Schilling, Achim; Gerum, Richard; Thievessen, Ingo; Winter, Lilli; et al. (EBioMedicine, 2019)
Background: Missense mutations in keratin 5 and 14 genes cause the severe skin fragility disorder epidermolysis bullosa simplex (EBS)by collapsing of the keratin cytoskeleton into cytoplasmic protein aggregates. Despite intense efforts, no molecular therapies are available, mostly due to the complex phenotype of EBS, comprising cell fragility, diminished adhesion, skin inflammation and itch. Methods: We extensively characterized KRT5 and KRT14 mutant keratinocytes from patients with severe generalized EBS following exposure to the chemical chaperone 4-phenylbutyrate (4-PBA). Findings: 4-PBA diminished keratin aggregates within EBS cells and ameliorated their inflammatory phenotype. Chemoproteomics of 4-PBA-treated and untreated EBS cells revealed reduced IL1β expression- but also showed activation of Wnt/β-catenin and NF-kB pathways. The abundance of extracellular matrix and cytoskeletal proteins was significantly altered, coinciding with diminished keratinocyte adhesion and migration in a 4-PBA dose-dependent manner. Interpretation: Together, our study reveals a complex interplay of benefits and disadvantages that challenge the use of 4-PBA in skin fragility disorders.
CRIS-Team Scopus Importer:2019-05-17
Keywords: 4-PBA; Epidermolysis bullosa; Keratinocyte; Keratins; Skin blistering

Twisting integrin receptors increases endothelin-1 gene expression in endothelial cells - Fabry, Ben; et al. (American Journal of Physiology-Cell Physiology, 2001)

Unbiased High-Precision Cell Mechanical Measurements with Microconstrictions - Lange, Janina; Metzner, Claus; Richter, Sebastian; Schneider, Werner; Spermann, Monika; Kolb, Thorsten; Whyte, Graeme; Fabry, Ben (Biophysical Journal, 2017)

Up-regulation of Rho/ROCK Signaling in Sarcoma Cells Drives Invasion and Increased Generation of Protrusive Forces - Roesel, Daniel; Brabek, Jan; Tolde, Ondrej; Mierke, Claudia; Paranhos Zitterbart, Daniel; Raupach, Carina; Bicanova, K.; Kollmannsberger, Philip; Pankova, D. V.; Vesely, Pavel; Folk, Petr; Fabry, Ben (Molecular Cancer Research, 2008)

Up-regulation of Rho/ROCK Signaling in Sarcoma Cells Drives Invasion and Increased Generation of Protrusive Forces - Roesel, Daniel; Brabek, Jan; Tolde, Ondrej; Mierke, Claudia; Paranhos Zitterbart, Daniel; Raupach, Carina; Bicanova, K.; Kollmannsberger, Philip; Pankova, D. V.; Vesely, Pavel; Folk, Petr; Fabry, Ben (Molecular Cancer Research, 2008)

Vinculin, cell mechanics, and tumor cell invasion - Goldmann, Wolfgang; Auernheimer, Vera; Thievessen, Ingo; Fabry, Ben (Cell Biology International, 2013)

Vinculin facilitates cell invasion into three-dimensional collagen matrices - Mierke, Claudia; Kollmannsberger, Philip; Paranhos Zitterbart, Daniel; Diez, Gerold; Koch, Thorsten; Marg, Susanna; Ziegler, Wolfgang H.; Goldmann, Wolfgang; Fabry, Ben (Journal of Chemical Biology, 2010)

Vinculin is required for cell polarization, migration, and extracellular matrix remodeling in 3D collagen - Thievessen, Ingo; Fakhri, Nikta; Steinwachs, Julian; Kraus, Viola; McIsaac, R. Scott; Gao, Liang; Chen, Bi-Chang; Baird, Michelle A.; Davidson, Michael W.; Betzig, Eric; Oldenbourg, Rudolf; Waterman, Clare M.; et al. (The FASEB Journal, 2015)

Vinculin phosphorylation at residues Y100 and Y1065 is required for cellular force transmission. - Auernheimer, Vera; Lautscham, Lena; Leidenberger, Maria; Friedrich, Oliver; Kappes, Bärbel; Fabry, Ben; Goldmann, Wolfgang (Journal of cell science, 2015)
The focal adhesion protein vinculin connects the actin cytoskeleton via talin and integrin with the extracellular matrix. Vinculin consists of a globular head and tail domain, which undergo conformational changes from a closed auto-inhibited conformation in the cytoplasm to an open conformation in focal adhesions. Src-phosphorylation has been suggested to regulate this conformational switch. To explore the role of phosphorylation in vinculin activation, we used knock-out mouse embryonic fibroblasts re-expressing different vinculin mutants in traction microscopy, magnetic tweezer microrheology, FRAP, and actin-binding assays. Compared to cells expressing wildtype or constitutively active vinculin, we found reduced tractions, cytoskeletal stiffness, adhesion strength, and increased vinculin dynamics in cells expressing constitutively inactive vinculin or vinculin where Src-phosphorylation was blocked by replacing tyrosine at position 100 and/or 1065 with non-phosphorylatable phenylalanine. Replacing tyrosines with phospho-mimicking glutamic acid restored cellular tractions, stiffness, adhesion strength as well as vinculin dynamics, and facilitated vinculin-actin binding. These data demonstrate that Src-phosphorylation is necessary for vinculin activation, and that phosphorylation controls cytoskeletal mechanics by regulating force transmission between the actin cytoskeleton and focal adhesion proteins.

Viscoelastic properties of suspended cells measured with shear flow deformation cytometry - Gerum, Richard; Mirzahossein, Elham; Eroles, Mar; Elsterer, Jennifer; Mainka, Astrid; Bauer, Andreas; Sonntag, Selina; Winterl, Alexander; Bartl, Johannes; Fischer, Lena; Abuhattum, Shada; Goswami, Ruchi; et al. (eLife, 2022)
Numerous cell functions are accompanied by phenotypic changes in viscoelastic prop-erties, and measuring them can help elucidate higher level cellular functions in health and disease. We present a high-throughput, simple and low-cost microfluidic method for quantitatively measuring the elastic (storage) and viscous (loss) modulus of individual cells. Cells are suspended in a high-viscosity fluid and are pumped with high pressure through a 5.8 cm long and 200 µm wide microflu-idic channel. The fluid shear stress induces large, ear ellipsoidal cell deformations. In addition, the flow profile in the channel causes the cells to rotate in a tank-treading manner. From the cell deformation and tank treading frequency, we extract the frequency-dependent viscoelastic cell properties based on a theoretical framework developed by R. Roscoe [1] that describes the deformation of a viscoelastic sphere in a viscous fluid under steady laminar flow. We confirm the accuracy of the method using atomic force microscopy-calibrated polyacrylamide beads and cells. Our measurements demonstrate that suspended cells exhibit power-law, soft glassy rheological behavior that is cell-cycle-dependent and mediated by the physical interplay between the actin filament and intermediate filament networks.
CRIS-Team Scopus Importer:2022-10-28